Laminate, antenna system and method for manufacturing same - Patents.com

The laminated body with polyvinyl acetal and ionomer resin adhesive layers addresses the issue of reduced transmission characteristics in high-frequency antenna systems by enhancing adhesiveness to glass substrates, improving GHz band performance and data transmission efficiency.

JP7623954B2Active Publication Date: 2025-01-29KURARAY AMERICA INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021562633
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-30
Filing Date
2020-11-30
Publication Date
2025-01-29
Estimated Expiration
2040-11-30

AI Technical Summary

Technical Problem

Existing antenna systems for high-frequency communication are limited by reduced transmission characteristics and attenuation of radio waves, particularly in the GHz band, due to the use of conventional materials that do not effectively adhere to glass substrates, leading to reduced transmission efficiency.

Method used

A laminated body comprising a high-frequency antenna circuit board with adhesive layers made of polyvinyl acetal resin and ionomer resin, which provide high adhesiveness to glass substrates, reducing attenuation and enhancing transmission characteristics in the GHz band.

Benefits of technology

The laminated body with polyvinyl acetal and ionomer resin adhesive layers effectively adheres to glass substrates, improving transmission characteristics and enabling high-frequency communication with reduced attenuation, allowing for larger data transmission capacities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623954000014
    Figure 0007623954000014
  • Figure 0007623954000015
    Figure 0007623954000015
  • Figure 0007623954000016
    Figure 0007623954000016
Patent Text Reader

Abstract

The present invention provides a multilayer body that is capable of forming an antenna system, which is useful for high frequency communication, by being bonded with a glass base material. The multilayer body (110) according to the present invention comprises: a high frequency antenna circuit board (117); and an adhesive layer (113) which is adjacent to at least one surface of the high frequency antenna circuit board (117), while being configured from at least one resin that is selected from the group consisting of polyvinyl acetal resins and ionomer resins.
Need to check novelty before this filing date? Find Prior Art

Description

Related Applications

[0001] This application claims priority to Japanese Patent Application No. 2019-218850, filed on December 3, 2019, and Japanese Patent Application No. 2020-129756, filed on July 30, 2020, the entire contents of which are incorporated herein by reference. [Technical field]

[0002] The present invention relates to a laminate comprising a radio frequency antenna circuit board for use in forming an antenna system useful for communicating at radio frequencies, as well as to an antenna system useful for communicating at radio frequencies and a method for making the same. [Background technology]

[0003] It is known to provide antennas for transmitting and receiving car telephones and mobile phones on moving objects such as automobiles. For example, Patent Document 1 (JP Patent Publication 2007-53505A) describes that an antenna made of conductive wires provided on the window glass surface or the surface of an insulating material on the body of a moving object such as an automobile is suitable for receiving radio waves such as UHF and VHF broadcast waves of television, and for transmitting and receiving wideband radio waves such as car phones, mobile phones, personal radio, commercial radio, and PHS. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-53505 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the amount of information that can be transmitted is limited for radio waves used in UHF and VHF broadcast waves, as well as for car phones, mobile phones, personal radio, commercial radio, PHS, etc. In recent years, the amount of information transmitted has been steadily increasing, and in order to transmit large amounts of information, it is necessary to use the high-frequency GHz band.

[0006] An object of the present invention is to provide a laminate that can form an antenna system having excellent transmission characteristics in the GHz band by bonding it to a glass substrate. Another object of the present invention is to provide an antenna system which is integrated with a glass layer and has excellent transmission characteristics in the GHz band, and a method for manufacturing the same. [Means for solving the problem]

[0007] In order to achieve the above object, the inventors of the present invention considered using a high frequency antenna circuit board having high accuracy for high frequencies, and discovered a new problem in that, because the transmission distance is shorter at high frequencies, the radio waves reaching the high frequency antenna circuit board are affected by obstacles that were not affected in the conventional MHz band, and thus attenuate. The inventors then discovered that in an antenna system in which a glass substrate and a high-frequency antenna circuit board are bonded together using an adhesive layer made of polyvinyl acetal resin or ionomer resin, which are materials that have high adhesion to glass substrates and a low dielectric constant, it is possible to utilize high frequencies with high precision by allowing radio waves to reach the high-frequency antenna circuit board from the glass substrate via the adhesive layer, which led to the completion of the present invention.

[0008] That is, the present invention can be configured in the following manner. [Aspect 1] A high frequency antenna circuit board; an adhesive layer adjacent to at least one surface of the high frequency antenna circuit board and made of at least one resin selected from the group consisting of polyvinyl acetal resin and ionomer resin; A laminate having [Aspect 2] 2. The laminate of embodiment 1, further comprising a protective layer. [Aspect 3] 3. The laminate of claim 2, wherein the protective layer is adjacent to the adhesive layer. Aspect 4 4. The laminate according to claim 2 or 3, wherein one of the outermost layers is composed of the adhesive layer, and the other is composed of the protective layer. Aspect 5 The laminate according to any one of aspects 2 to 4, wherein the protective layer is made of glass or a polyester resin. Aspect 6 A laminate according to any one of aspects 1 to 5, wherein the total thickness of at least one of the adhesive layers is 370 μm or less (preferably 1 to 300 μm, more preferably 5 to 200 μm, even more preferably 10 to 100 μm, even more preferably 20 to 60 μm, particularly preferably 20 μm or more but less than 50 μm, particularly preferably 20 to 45 μm, and most preferably 20 to 40 μm). Aspect 7 A laminate according to any one of aspects 1 to 6, wherein at least one of the adhesive layers is made of a polyvinyl acetal resin having a plasticizer content of 0 to 30% by mass (preferably 0 to 20% by mass, more preferably 0 to 15% by mass, even more preferably 0 to 10% by mass, and even more preferably 0 to 5% by mass). Aspect 8 A laminate according to any one of aspects 1 to 7, wherein at least one of the adhesive layers is made of a polyvinyl acetal resin, and the viscosity of a 10 mass % solution of the polyvinyl acetal resin in a toluene / ethanol = 1 / 1 (mass ratio) measured at 20°C and 30 rpm using a Brookfield (B-type) viscometer is 100 to 1000 mPa s (preferably 120 to 800 mPa s, more preferably 150 to 600 mPa s, even more preferably 180 to 500 mPa s, and even more preferably 200 to 400 mPa s). Aspect 9 A laminate according to any one of aspects 1 to 8, wherein an adhesive layer (1) and an adhesive layer (2) are adjacent to each other on both sides of a high-frequency antenna circuit board, the adhesive layer (1) has a total thickness of 370 μm or less (preferably 1 to 300 μm, more preferably 5 to 200 μm, even more preferably 10 to 100 μm, even more preferably 20 to 60 μm, particularly preferably 20 μm or more and less than 50 μm, particularly preferably 20 to 45 μm, and most preferably 20 to 40 μm), and the adhesive layer (2) has a total thickness of more than 370 μm and 2.5 mm or less (preferably 380 μm to 2.28 mm, more preferably 500 μm to 1.6 mm, and even more preferably 750 to 850 μm). Aspect 10 10. The laminate according to any one of aspects 1 to 9, wherein the high-frequency antenna circuit board includes an insulating layer made of at least one material selected from the group consisting of a thermoplastic liquid crystal polymer, a polyimide, a polyether ether ketone, a polyphenylene ether, a fluororesin, and a ceramic. Aspect 11 11. The laminate according to any one of the first to tenth embodiments, wherein the high-frequency antenna circuit board is capable of supporting a data transmission speed of 10 gigabits per second or more. Aspect 12 12. The laminate according to any one of the first to eleventh embodiments, which is used to form an antenna system by application to an adherend. Aspect 13 13. The laminate according to claim 12, wherein the adherend is a glass substrate and is bonded via the adhesive layer. Aspect 14 A laminate according to any one of aspects 1 to 13; a first glass layer adjacent to the adhesive layer and having a higher dielectric constant than the adhesive layer; An antenna system comprising: Aspect 15 An antenna system as described in embodiment 14, further comprising a second glass layer, wherein the high-frequency antenna circuit board is disposed between the first glass layer and the second glass layer via a first adhesive layer and a second adhesive layer, respectively. Aspect 16 16. The antenna system of claim 14, wherein the first glass layer is made of at least one glass selected from the group consisting of soda-lime glass, borate glass, borosilicate glass, aluminosilicate glass, quartz glass, alkali-free glass, and low-alkali glass. Aspect 17 The antenna system according to any one of aspects 14 to 16, wherein the dielectric constant εg of the first glass layer, measured at a frequency of 28 GHz in both one direction in a plane and in a direction perpendicular thereto, is 3.0 to 7.5 (preferably 4.0 to 7.5, more preferably 4.5 to 7.5, even more preferably 5.5 to 7.5, still more preferably 5.8 to 7.3, and particularly preferably 6.0 to 7.0). Aspect 18 18. The antenna system according to any one of aspects 14 to 17, wherein the antenna circuit in the high-frequency antenna circuit board is disposed in a region within 10 cm inward from the edge of the glass layer. Aspect 19 The antenna system according to any one of aspects 14 to 18, wherein the first glass layer includes a colored region, and an antenna circuit in the high-frequency antenna circuit board is disposed within the colored region. Aspect 20 A method for producing the antenna system according to any one of aspects 14 to 19, comprising the steps of: A step of overlapping a high frequency antenna circuit board on at least one glass substrate via an adhesive layer and / or adhesive film composed of at least one type selected from the group consisting of polyvinyl acetal resins and ionomer resins; A step of heating and pressing the adhesive layer and / or the adhesive film at a temperature equal to or higher than the softening temperature thereof; A method for manufacturing an antenna system comprising: Aspect 21 A method for producing the antenna system according to any one of aspects 14 to 19, comprising the steps of: A step of interposing a compound absorbable by the adhesive layer between the adhesive layer of the outermost layer of the laminate according to any one of aspects 1 to 13 and a glass substrate, and allowing the adhesive layer to absorb the compound, thereby adhering the laminate to the glass substrate; A method for manufacturing an antenna system comprising: Aspect 22 22. The method of claim 21, wherein the compound is a plasticizer for the adhesive layer. Aspect 23 An adhesive film made of at least one resin selected from the group consisting of polyvinyl acetal resins and ionomer resins, the adhesive film being used as an adhesive layer in the antenna system according to any one of aspects 14 to 19.

[0009] It should be noted that any combination of at least two elements disclosed in the claims and / or the specification and / or the drawings is included in the present invention. In particular, any combination of two or more of the claims described in the claims is included in the present invention. Effect of the Invention

[0010] According to the laminate of the present invention, the adhesive layer adjacent to the high-frequency antenna circuit board is made of a specific resin, which provides excellent adhesion to glass substrates and allows efficient transmission of high frequencies at the interface with the glass, making it possible to configure an antenna system with excellent transmission characteristics in the GHz band. Furthermore, according to the present invention, in an antenna system, a high-frequency antenna circuit board is provided and a glass layer is provided on the high-frequency antenna circuit board via an adhesive layer made of a specific resin, thereby suppressing high-frequency attenuation and improving the transmission characteristics of the high-frequency antenna circuit board, making it possible to exchange large amounts of information. [Brief description of the drawings]

[0011] The present invention will be more clearly understood from the following description of preferred embodiments with reference to the accompanying drawings. However, the embodiments and drawings are merely for illustration and explanation, and should not be used to define the scope of the present invention. The scope of the present invention is defined by the accompanying claims. In the accompanying drawings, the same part numbers in multiple drawings indicate the same parts. The drawings are not necessarily drawn to scale, and are exaggerated to illustrate the principles of the present invention. [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating a laminate according to a first embodiment of the present invention. [Diagram 2] FIG. 4 is a schematic cross-sectional view illustrating a laminate according to a second embodiment of the present invention. [Diagram 3] FIG. 11 is a schematic cross-sectional view illustrating a laminate according to a third embodiment of the present invention. [Figure 4] FIG. 11 is a schematic cross-sectional view illustrating a laminate according to a fourth embodiment of the present invention. [Diagram 5] FIG. 11 is a schematic cross-sectional view for explaining an antenna system according to a fifth embodiment of the present invention. [Figure 6] FIG. 13 is a schematic cross-sectional view illustrating an antenna system according to a sixth embodiment of the present invention. [Figure 7] FIG. 13 is a schematic cross-sectional view illustrating an antenna system according to a seventh embodiment of the present invention. [Figure 8] FIG. 13 is a schematic cross-sectional view illustrating an antenna system according to an eighth embodiment of the present invention. [Figure 9] FIG. 13 is a schematic cross-sectional view for explaining an antenna system according to a ninth embodiment of the present invention. [Figure 10] FIG. 16 is a schematic cross-sectional view for explaining an antenna system according to a tenth embodiment of the present invention. [Figure 11] FIG. 23 is a schematic cross-sectional view for explaining an antenna system according to an eleventh embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] <Laminate> The laminate of the present invention comprises at least a high-frequency antenna circuit board and an adhesive layer adjacent to at least one surface of the high-frequency antenna circuit board, the adhesive layer being composed of at least one selected from the group consisting of polyvinyl acetal resin and ionomer resin. Since the adhesive layer of the laminate of the present invention is composed of polyvinyl acetal resin and / or ionomer resin, which are materials having high adhesion to glass substrates and a lower dielectric constant than glass substrates, it is possible to form an antenna system having excellent transmission characteristics in the GHz band by adhering the high-frequency antenna circuit board to the glass substrate via the adhesive layer. In the laminate of the present invention, one or more high-frequency antenna circuit boards may be attached to the adhesive layer in a laminated state.

[0013] Specific embodiments of the laminate of the present invention will be described with reference to the drawings, but the laminate of the present invention is not limited to the exemplified embodiments.

[0014] [First embodiment] Fig. 1 is a schematic cross-sectional view for explaining a laminate according to a first embodiment. As shown in Fig. 1, a laminate 110 according to the first embodiment includes a high-frequency antenna circuit board 117 and an adhesive layer 113 composed of at least one resin selected from the group consisting of polyvinyl acetal resin and ionomer resin. The adhesive layer 113 is adjacent to one surface of the high-frequency antenna circuit board 117.

[0015] The adhesive layer 113 of the laminate 110 can be adjacently adhered to a glass substrate to form an antenna system having a high frequency antenna circuit board 117 disposed on the glass substrate.

[0016] The high frequency antenna circuit board 117 includes a high frequency insulating layer (hereinafter, sometimes simply referred to as an insulating layer) 115, a circuit layer 114 disposed on one surface (the surface on the adhesive layer 113 side) of the insulating layer 115, and a conductor layer 116 disposed on the other surface (the surface opposite to the adhesive layer 113) of the insulating layer 115. Although only one circuit layer is shown in FIG. 1 for simplification, the insulating layer may include an inner layer circuit (not shown), and therefore the high frequency antenna circuit board 117 may be a multi-layer circuit board. Furthermore, the conductor layer 116 may have a circuit pattern as necessary, or may be a reflective metal layer.

[0017] The adhesive layer 113 is adhered to the high frequency antenna circuit board 117. In Fig. 1, the adhesive layer 113 is in contact with the circuit portion (circuit layer 114) and the non-circuit portion (insulating layer 115) of the high frequency antenna circuit board 117, and it is sufficient for the adhesive layer 113 to have adhesiveness to at least one of them, and it is preferable for the adhesive layer 113 to be adhered to both.

[0018] The adhesive layer 113 may have a desired size relative to the radio frequency antenna circuit board 117 depending on the application. As shown in FIG. 1, the dimension of the adhesive layer 113 in the planar direction may be the same as, smaller than, or larger than the radio frequency antenna circuit board 117. When the adhesive layer 113 is larger in the planar direction than the radio frequency antenna circuit board 117, the radio frequency antenna circuit board 117 may be embedded in the adhesive layer 113. The planar direction is a planar direction normal to the thickness direction Z in FIG. 1. The dimensions of the adhesive layer and the radio frequency antenna circuit board are common to the following embodiments.

[0019] In the laminate 110, the adhesive layer 113 has a thickness df (total thickness da) on the high frequency antenna circuit board 117 in the thickness direction Z. Here, when the ratio of the circuit part (circuit layer 114) to the surface is less than half, the thickness df of the adhesive layer 113 is the thickness up to the insulating layer 115 ignoring the circuit part, and this is also common to the following embodiments. In addition, the insulating layer 115 in the high frequency antenna circuit board 117 has a thickness dp. The thickness dp of the insulating layer 115 is the total thickness of the insulating layers in the antenna circuit board, that is, the total thickness of all the insulating layers of the antenna circuit board. In FIG. 1, the total thickness da of the adhesive layer 113 is shown to be the same thickness as the thickness df on the high frequency antenna circuit board 117, but for example, when the high frequency antenna circuit board 117 is embedded, it indicates the maximum thickness of the adhesive layer 113 in the thickness direction Z, rather than using the surface in contact with the insulating layer 115 as a reference.

[0020] [Second embodiment] FIG. 2 is a schematic cross-sectional view for explaining a laminate according to a second embodiment. As shown in FIG. 2, a laminate 210 according to the second embodiment includes a high-frequency antenna circuit board 117 and a first adhesive layer 213a and a second adhesive layer 213b disposed on both sides of the high-frequency antenna circuit board 117. The first adhesive layer 213a and the second adhesive layer 213b are the same or different and are composed of at least one selected from the group consisting of polyvinyl acetal resin and ionomer resin. The first adhesive layer 213a is adjacent to one side of the high-frequency antenna circuit board 117, and the second adhesive layer 213b is adjacent to the other side of the high-frequency antenna circuit board 117. The first adhesive layer 213a and the second adhesive layer 213b may be directly or indirectly bonded to both sides of the high-frequency antenna circuit board 117, respectively, or may be attached via other fixing means (not shown). The same components as those in the first embodiment are denoted by the same reference numerals, and the description thereof will be omitted.

[0021] At least one of the first adhesive layer 213a and the second adhesive layer 213b of the laminate 210 is adjacent to a glass substrate and bonded to the glass substrate to form an antenna system in which the high frequency antenna circuit board 117 is disposed on the glass substrate. For example, one adhesive layer of the laminate 210 may be bonded to the glass substrate, and the other adhesive layer may be used as is. Alternatively, the first adhesive layer 213a and the second adhesive layer 213b of the laminate 210 may be bonded to separate glass substrates to form a laminated glass.

[0022] 2, the first adhesive layer 213a is in contact with the circuit portion (circuit layer 114) and the non-circuit portion (insulating layer 115) of the high frequency antenna circuit board 117, and is preferably adhered to both, although it is sufficient for the first adhesive layer 213a to have adhesiveness to at least one of them. The second adhesive layer 213b is adhered to the conductor layer 116 of the high frequency antenna circuit board 117.

[0023] The first adhesive layer 213a and the second adhesive layer 213b may have the same or different constituent materials, thicknesses, surface dimensions, etc. Furthermore, the first adhesive layer 213a and the second adhesive layer 213b may each have a desired size relative to the high frequency antenna circuit board 117 depending on the application. In FIG. 2, the surface dimensions of the first adhesive layer 213a and the second adhesive layer 213b are both the same as the high frequency antenna circuit board 117, but may each be larger than the surface dimensions of the high frequency antenna circuit board 117 in order to protect the high frequency antenna circuit board.

[0024] In the laminate 210, in the thickness direction Z, the first adhesive layer 213a has a thickness df (total thickness da) on the high frequency antenna circuit board 117, the insulating layer 115 in the high frequency antenna circuit board 117 has a thickness dp, and the second adhesive layer 213b has a thickness df' (total thickness da') on the high frequency antenna circuit board 117. Here, the thickness df of the first adhesive layer 213a is the thickness up to the insulating layer 115 ignoring the circuit part, since the ratio of the circuit part (circuit layer 114) to the surface is less than half. In addition, the thickness df' of the second adhesive layer 213b is the thickness up to the conductive layer 116, since the ratio of the conductive layer 116 to the surface is more than half. In Figure 2, the total thickness da of the first adhesive layer 213a and the total thickness da' of the second adhesive layer 213b are shown to be the same thicknesses as the thicknesses df and df' on the high-frequency antenna circuit board 117, respectively.However, for example, when the high-frequency antenna circuit board 117 is embedded, the thicknesses indicate the maximum thicknesses of the first adhesive layer 213a and the second adhesive layer 213b in the thickness direction Z, rather than being based on the surfaces in contact with the insulating layer 115 or the conductor layer 116.

[0025] [Third embodiment] FIG. 3 is a schematic cross-sectional view for explaining a laminate according to a third embodiment. As shown in FIG. 3, a laminate 310 according to the third embodiment includes a high-frequency antenna circuit board 117, a first adhesive layer 313a and a second adhesive layer 313b disposed on both sides of the high-frequency antenna circuit board 117, and a protective layer 318. The first adhesive layer 313a and the second adhesive layer 313b are the same or different and are composed of at least one selected from the group consisting of polyvinyl acetal resin and ionomer resin. The first adhesive layer 313a is adjacent to one side of the high-frequency antenna circuit board 117, and the second adhesive layer 313b is adjacent to the other side of the high-frequency antenna circuit board 117. The protective layer 318 is adjacent to the second adhesive layer 313b. The first adhesive layer 313a and the second adhesive layer 313b may be directly attached to both sides of the high frequency antenna circuit board 117, or may be attached via other fixing means (not shown). The protective layer 318 may be directly attached to the second adhesive layer 313b, or may be attached via other fixing means (not shown). The same components as those in the first embodiment are denoted by the same reference numerals, and the description thereof will be omitted.

[0026] The first adhesive layer 313a of the laminate 310 can be adjacently adhered to a glass substrate to form an antenna system having a high frequency antenna circuit board 117 disposed on the glass substrate.

[0027] The first adhesive layer 313a is adhered to one surface of the high frequency antenna circuit board 117. In Fig. 3, the first adhesive layer 313a is in contact with the circuit portion (circuit layer 114) and the non-circuit portion (insulating layer 115) of the high frequency antenna circuit board 117, and it is sufficient for the first adhesive layer 313a to have adhesiveness to at least one of them, and it is preferable for the first adhesive layer 313a to be adhered to both. The second adhesive layer 313b is adhered to the other surface (conductor layer 116) and protective layer 318 of the high frequency antenna circuit board 117.

[0028] The first adhesive layer 313a and the second adhesive layer 313b may be the same as each other in terms of constituent material, thickness, surface dimension, etc., or may be different. The first adhesive layer 313a and the second adhesive layer 313b may have a desired size depending on the application, relative to the high frequency antenna circuit board 117. In FIG. 3, the surface dimensions of the first adhesive layer 313a and the second adhesive layer 313b are both the same as the high frequency antenna circuit board 117, but may be larger than the surface dimensions of the high frequency antenna circuit board 117.

[0029] By providing the protective layer 318, the high frequency antenna circuit board 117 can be protected from water, moisture, scratches, adhesion of dust, etc., before and after the formation of the antenna system. From the viewpoint of protecting the high frequency antenna circuit board 117, the protective layer 318 may be fixed to one surface of the high frequency antenna circuit board 117 via a second adhesive layer 313b made of polyvinyl acetal resin or ionomer resin, or may be bonded via a fixing means made of a material other than polyvinyl acetal resin or ionomer resin and capable of bonding the high frequency antenna circuit board 117 and the protective layer 318, or the protective layer 318 may be directly bonded to the high frequency antenna circuit board 117, or the protective layer may be attached to the high frequency antenna circuit board by various fixing means.

[0030] In the laminate 310, in the thickness direction Z, the first adhesive layer 313a has a thickness df (total thickness da) on the high frequency antenna circuit board 117, the insulating layer 115 in the high frequency antenna circuit board 117 has a thickness dp, the second adhesive layer 313b has a thickness df' (total thickness da') on the high frequency antenna circuit board 117, and the protective layer 318 has a thickness dc. Here, the thickness df of the first adhesive layer 313a is the thickness up to the insulating layer 115 ignoring the circuit part, since the ratio of the circuit part (circuit layer 114) in the plane is less than half. In addition, the thickness df' of the second adhesive layer 313b is the thickness from the surface in contact with the protective layer 318 to the conductive layer 116, since the ratio of the conductive layer 116 in the plane is more than half. The total thickness da of the first adhesive layer 313a and the total thickness da' of the second adhesive layer 313b are the same as the thicknesses df and df' on the high frequency antenna circuit board 117, respectively.

[0031] [Fourth embodiment] Fig. 4 is a schematic cross-sectional view for explaining a laminate according to the fourth embodiment. As shown in Fig. 4, a laminate 410 according to the fourth embodiment includes a high-frequency antenna circuit board 117, an adhesive layer 413 composed of at least one selected from the group consisting of a polyvinyl acetal resin and an ionomer resin, and a protective layer 418. The adhesive layer 413 is adjacent to one surface of the high-frequency antenna circuit board 117. The protective layer 418 is adjacent to the adhesive layer 413. Note that the same components as those in the first embodiment are denoted by the same reference numerals, and their description will be omitted.

[0032] The protective layer 418 can protect the adhesive layer 413 from scratches and adhesion of dust. The protective layer 418 can be peeled off from the adhesive layer 413, and when the laminate 410 is used to form an antenna system, the protective layer 418 is peeled off from the adhesive layer 413 and the exposed adhesive layer 413 is bonded adjacent to a glass substrate, thereby forming an antenna system in which the high frequency antenna circuit board 117 is disposed on the glass substrate.

[0033] The adhesive layer 413 is adhered to the high frequency antenna circuit board 117. In Fig. 4, the adhesive layer 413 is in contact with the circuit portion (circuit layer 114) and the non-circuit portion (insulating layer 115) of the high frequency antenna circuit board 117, and it is sufficient for the adhesive layer 413 to have adhesiveness to at least one of them, and it is preferable for the adhesive layer 413 to be adhered to both.

[0034] The adhesive layer 413 may have a desired size depending on the application, relative to the high frequency antenna circuit board 117. As shown in Fig. 4, the dimension of the adhesive layer 413 in the planar direction may be the same as, smaller than, or larger than the high frequency antenna circuit board 117. When the adhesive layer 413 is larger than the high frequency antenna circuit board 117 in the planar direction, the protective layer 418 may also have a similar dimension to the adhesive layer 413.

[0035] In the laminate 410, in the thickness direction Z, the adhesive layer 413 has a thickness df (total thickness da) on the high frequency antenna circuit board 117. The insulating layer 115 in the high frequency antenna circuit board 117 has a thickness dp, and the protective layer 418 has a thickness dc. Here, the thickness df of the adhesive layer 413 on the high frequency antenna circuit board 117 is the thickness from the surface in contact with the protective layer 418 to the insulating layer 115, since the ratio of the thickness to the surface of the circuit portion (circuit layer 114) is less than half. The total thickness da of the adhesive layer 413 indicates the same thickness as the thickness df on the high frequency antenna circuit board 117.

[0036] Each component will be described below, however, these are merely examples and various modifications may be included as long as the effects of the present invention can be achieved.

[0037] (adhesive layer) The adhesive layer is composed of at least one selected from the group consisting of polyvinyl acetal resins and ionomer resins. These resins have high and stable adhesive strength to glass substrates, making them suitable for forming antenna systems. In addition, they have good conformability to curved glass such as automobile windshields, making it possible to suppress foaming and peeling, and also to suppress disconnection and deformation of the circuit of the high-frequency antenna circuit board during bonding, thereby suppressing deterioration of antenna performance. Furthermore, these resins have high transparency, making it possible to reduce obstruction of the field of view.

[0038] In addition, the polyvinyl acetal resin and the ionomer resin have a low dielectric constant, which is lower than that of a glass substrate that is generally used at the same frequency. By bonding the glass substrate and the radio frequency antenna circuit board via an adhesive layer made of such a resin, the reflectance R of the radio frequency incident from the glass substrate until it reaches the surface of the radio frequency antenna circuit board can be reduced, and the proportion of the radio frequency reaching the radio frequency antenna circuit board can be increased.

[0039] For example, at a frequency of 28 GHz, the dielectric constant εf of the adhesive layer may be, for example, 2.0 to 4.0, preferably 2.2 to 3.5, and more preferably 2.4 to 3.0.

[0040] Furthermore, for example, at a frequency of 28 GHz, the dielectric tangent tan δf of the adhesive layer may be, for example, 0.05 or less, and preferably 0.03 or less.

[0041] The dielectric properties (dielectric constant and dielectric loss tangent) can be measured at 28 GHz (25°C) in accordance with JIS R 1660-2 using a Fabry-Perot resonator (Model No. DPS03) manufactured by Keycom Co., Ltd. This measurement method allows for highly accurate measurements in one direction on a plane and in both directions perpendicular to that direction (XY directions), and even objects with low tan δ can be measured with high accuracy.

[0042] The thickness df (df') of the adhesive layer on the high-frequency antenna circuit board can be selected from a wide range of about 1 μm to 20.0 mm, and from the viewpoint of suppressing reflectance, it may be, for example, about 0.1 to 20.0 mm, preferably about 0.1 to 10.0 mm, and more preferably about 0.15 to 2.0 mm.

[0043] In one embodiment, the thickness df1 (df1') of the adhesive layer (1) on the high frequency antenna circuit board is preferably 370 μm or less, more preferably 300 μm or less, even more preferably 200 μm or less, even more preferably 100 μm or less, particularly preferably 60 μm or less, particularly more preferably less than 50 μm, particularly more preferably 45 μm or less, and most preferably 40 μm or less. The thickness df1 (df1') of the adhesive layer (1) on the high frequency antenna circuit board is preferably 1 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, and even more preferably 20 μm or more. In this specification, the adhesive layer (1) refers to an adhesive layer having a thickness in the above range.

[0044] In another embodiment, the thickness df2 (df2') of the adhesive layer (2) on the high frequency antenna circuit board is preferably more than 370 μm, more preferably 500 μm or more, and even more preferably 750 μm or more, from the viewpoint of suppressing reflectance. The thickness df2 (df2') of the adhesive layer (2) on the high frequency antenna circuit board is preferably 2.5 mm or less, more preferably 2.28 mm or less, even more preferably 1.6 mm or less, and even more preferably 0.85 mm or less. In this specification, the adhesive layer (2) refers to an adhesive layer having a thickness in the above range.

[0045] Furthermore, the total thickness da (da') of the adhesive layer can be selected from a wide range of about 1 μm to 20.0 mm, and may be, for example, about 0.1 to 20.0 mm, preferably about 0.1 to 10.0 mm, and more preferably about 0.15 to 2.0 mm.

[0046] In one embodiment, the total thickness da1 (da1') of the adhesive layer (1) is preferably 370 μm or less, more preferably 300 μm or less, even more preferably 200 μm or less, even more preferably 100 μm or less, particularly preferably 60 μm or less, particularly more preferably less than 50 μm, particularly more preferably 45 μm or less, and most preferably 40 μm or less, as a viewpoint of suppressing reflectivity and thinning the thickness of the antenna system. The total thickness da1 (da1') of the adhesive layer (1) is preferably 1 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, and even more preferably 20 μm or more. Even if the adhesive layer is thin in this way, since it is made of a specific resin, it can be made to appropriately follow the unevenness of the circuit of the high frequency antenna circuit board, and thus the generation of air bubbles (remaining air) can be suppressed.

[0047] In another embodiment, the total thickness da2 (da2') of the adhesive layer (2) is preferably more than 370 μm, more preferably 500 μm or more, and even more preferably 750 μm or more, from the viewpoint of embedding a high-frequency antenna circuit board. The total thickness da2 (da2') of the adhesive layer (2) is preferably 2.5 mm or less, more preferably 2.28 mm or less, even more preferably 1.6 mm or less, and even more preferably 0.85 mm or less.

[0048] When a first adhesive layer and a second adhesive layer are adjacent to both sides of the high frequency antenna circuit board, respectively, both the first adhesive layer and the second adhesive layer may be adhesive layer (1) or adhesive layer (2). In addition, the first adhesive layer may be adhesive layer (1) and the second adhesive layer may be adhesive layer (2), and when a laminated glass having a high frequency antenna circuit board disposed therein is formed by thinning one of the adhesive layers, it is possible to produce the laminated glass without hollowing out the interlayer film for laminated glass to fill the step or without using a spacer to fill the step.

[0049] The adhesive layer may contain at least one resin selected from the group consisting of polyvinyl acetal resins and ionomer resins in an amount of 50% by mass or more, preferably 60% by mass or more, and more preferably 70% by mass or more.

[0050] (Polyvinyl acetal resin) Examples of polyvinyl acetal resins include polyvinyl acetal resins produced by acetalization of vinyl alcohol-based resins such as polyvinyl alcohol or vinyl alcohol copolymers. When the adhesive layer contains a polyvinyl acetal resin, it may contain one type of polyvinyl acetal resin, or it may contain two or more polyvinyl acetal resins that are different in at least one of the viscosity average polymerization degree, acetalization degree, acetyl group amount, hydroxyl group amount, ethylene content, molecular weight of the aldehyde used for acetalization, and chain length. When the polyvinyl acetal resin contains two or more different polyvinyl acetal resins, it is preferable from the viewpoint of ease of melt molding to be a mixture of two or more polyvinyl acetal resins that are different in at least one of the viscosity average polymerization degree, acetalization degree, acetyl group amount, and hydroxyl group amount.

[0051] The polyvinyl acetal resin used in the present invention can be obtained by a known or conventional method, for example, an acetalization reaction is carried out by adding an aldehyde (or a keto compound) and an acid catalyst to an aqueous solution of polyvinyl alcohol or a vinyl alcohol copolymer. The reaction solution is then filtered as necessary, neutralized by adding a neutralizing agent such as an alkali, and the resin is filtered, washed with water and dried to obtain a polyvinyl acetal resin.

[0052] Polyvinyl alcohol can be obtained by saponifying a polyvinyl ester obtained by polymerizing a vinyl ester compound, and a vinyl alcohol copolymer can be obtained by saponifying a copolymer of a vinyl ester compound and another monomer.

[0053] Examples of vinyl ester compounds include vinyl acetate, 1-propenyl acetate, 1-methylvinyl acetate, 1-butenyl acetate, 2-methyl-1-propenyl acetate, vinyl propionate, vinyl butanoate, vinyl pivalate, vinyl versatate, vinyl pentanoate, vinyl hexanoate, vinyl octanoate, vinyl decanoate, vinyl dodecanoate, vinyl hexadecanoate, vinyl octadecanoate, and other aliphatic vinyl carboxylates, and vinyl aromatic vinyl carboxylates, such as vinyl benzoate. These vinyl ester compounds can be used alone or in combination. Among these vinyl ester compounds, vinyl acetate is preferred from the viewpoint of productivity.

[0054] Examples of other monomers include α-olefins such as ethylene, propylene, n-butene, and isobutylene; acrylic acid and its salts; acrylic acid esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, i-butyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate; methacrylic acid and its salts; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, Methacrylic acid esters such as i-propyl methacrylate, n-butyl methacrylate, i-butyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate; acrylamide; N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetone acrylamide, acrylamidopropanesulfonic acid and its salts, acrylamidopropyldimethylamine and its salts or its quaternary salts, N-methylolacrylamide, methacrylamide derivatives such as methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, methacrylamidepropanesulfonic acid and its salts, methacrylamidepropyldimethylamine and its salts or its quaternary salts, N-methylolmethacrylamide and its derivatives; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; nitriles such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride and vinyl fluoride; vinylidene halides such as vinylidene chloride and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and fumaric acid and their salts, esters, or anhydrides; and vinyl silyl compounds such as vinyltrimethoxysilane. The other monomers can be used alone or in combination of two or more thereof, and among these, ethylene is preferred as the other monomer.

[0055] The acid catalyst used in the acetalization reaction is not particularly limited, and any of organic and inorganic acids can be used, such as acetic acid, paratoluenesulfonic acid, nitric acid, sulfuric acid, hydrochloric acid, etc. Among them, hydrochloric acid, sulfuric acid, and nitric acid are preferred from the viewpoints of acid strength and ease of removal during washing.

[0056] The aldehyde (or keto compound) used in the production of the polyvinyl acetal resin is preferably linear, branched or cyclic having 1 to 10 carbon atoms, more preferably linear or branched. This results in a corresponding linear or branched acetal side chain. The polyvinyl acetal resin used in the present invention may be obtained by acetalizing polyvinyl alcohol or a vinyl alcohol copolymer with a mixture of a plurality of aldehydes (or keto compounds). The polyvinyl alcohol or the vinyl alcohol copolymer may be composed of only one of them, or may be a mixture of polyvinyl alcohol and a vinyl alcohol copolymer.

[0057] Examples of the aldehyde include aliphatic, aromatic, and alicyclic aldehydes such as formaldehyde, acetaldehyde, propionaldehyde, n-butyl aldehyde, isobutyl aldehyde, valeraldehyde, isovaleraldehyde, n-hexyl aldehyde, 2-ethylbutyl aldehyde, n-heptyl aldehyde, n-octyl aldehyde, 2-ethylhexyl aldehyde, n-nonyl aldehyde, n-decyl aldehyde, benzaldehyde, and cinnamaldehyde. Among them, aliphatic unbranched aldehydes having 2 to 6 carbon atoms are preferred, and n-butyl aldehyde is particularly preferred from the viewpoint of easily obtaining a polyvinyl acetal resin having a suitable breaking energy. These aldehydes can be used alone or in combination of two or more. Furthermore, polyfunctional aldehydes or aldehydes having other functional groups may be used in combination in an amount of 20% by mass or less of the total aldehydes. When n-butylaldehyde is used, the content of n-butylaldehyde in the aldehyde used for acetalization is preferably 50% by mass or more, more preferably 80% by mass or more, further preferably 95% by mass or more, particularly preferably 99% by mass or more, and may be 100% by mass.

[0058] The viscosity average degree of polymerization of the polyvinyl alcohol used as the raw material for the polyvinyl acetal resin is preferably 100 or more, more preferably 300 or more, more preferably 400 or more, even more preferably 600 or more, particularly preferably 700 or more, and most preferably 750 or more. When a polyvinyl acetal resin composition containing a large amount of plasticizer (for example, 20 parts by mass or more) is used as the polyvinyl acetal resin constituting the adhesive layer (2), the viscosity average degree of polymerization of the polyvinyl alcohol used as the raw material for the polyvinyl acetal resin is preferably 500 or more, more preferably 900 or more, more preferably 1000 or more, even more preferably 1200 or more, particularly preferably 1500 or more, and most preferably 1600 or more. The viscosity average degree of polymerization of polyvinyl alcohol is preferably 5,000 or less, more preferably 3,000 or less, even more preferably 2,500 or less, particularly preferably 2,300 or less, and most preferably 2,000 or less. The viscosity average degree of polymerization of polyvinyl alcohol can be measured, for example, based on JIS K 6726 "Testing method for polyvinyl alcohol".

[0059] Usually, the viscosity average degree of polymerization of the polyvinyl acetal resin is equal to that of the raw material polyvinyl alcohol, and therefore the preferred viscosity average degree of polymerization of the polyvinyl alcohol is equal to that of the polyvinyl acetal resin. When the adhesive layer contains two or more different polyvinyl acetal resins, it is preferable that the viscosity average degree of polymerization of at least one of the polyvinyl acetal resins is equal to or greater than the lower limit and equal to or less than the upper limit.

[0060] The amount of acetyl groups in the polyvinyl acetal resin constituting the adhesive layer may be preferably 0.01 to 20% by mass, more preferably 0.05 to 10% by mass, and even more preferably 0.1 to 5% by mass, as the mass of vinyl acetate units. The amount of acetyl groups in the polyvinyl acetal resin can be adjusted by appropriately adjusting the degree of saponification of the raw material polyvinyl alcohol or vinyl alcohol copolymer. When the adhesive layer contains two or more different polyvinyl acetal resins, it is preferable that the amount of acetyl groups in at least one of the polyvinyl acetal resins is within the above range, and particularly from the viewpoint of compatibility, it is particularly preferable that the difference in the amount of acetyl groups in each polyvinyl acetal resin is 1 mol % or less.

[0061] The degree of acetalization of the polyvinyl acetal resin used in the present invention is not particularly limited, but is preferably 40 to 86 mol%, more preferably 45 to 82 mol%, further preferably 50 to 78 mol%, particularly preferably 60 to 74 mol%, and most preferably 68 to 74 mol%. By appropriately adjusting the amount of aldehyde used when acetalizing the polyvinyl alcohol resin, the degree of acetalization of the polyvinyl acetal resin can be adjusted within the above range. When the degree of acetalization is within the above range, the compatibility of the polyvinyl acetal resin with the plasticizer is unlikely to decrease. When the adhesive layer contains two or more different polyvinyl acetal resins, it is preferable that the degree of acetalization of at least one of the polyvinyl acetal resins is within the above range, and particularly from the viewpoint of compatibility, the difference in the degree of acetalization of each polyvinyl acetal resin is preferably 2 mol% or less, and particularly preferably 1 mol% or less. The degree of acetalization is the amount of the above units that form acetal based on a repeating unit consisting of two carbon atoms in the main chain of a polyvinyl alcohol resin, which is a raw material for producing a polyvinyl acetal resin (e.g., a vinyl alcohol unit, a vinyl acetate unit, an ethylene unit, etc.).

[0062] The amount of hydroxyl groups in the polyvinyl acetal resin is preferably 6 to 26% by mass, more preferably 12 to 24% by mass, more preferably 15 to 22% by mass, and particularly preferably 18 to 21% by mass, as the mass of the vinyl alcohol unit. The amount of hydroxyl groups can be adjusted within the above range by adjusting the amount of aldehyde used when acetalizing the polyvinyl alcohol resin. When the adhesive layer contains two or more different polyvinyl acetal resins, it is preferable that the amount of hydroxyl groups in at least one of the polyvinyl acetal resins is within the above range.

[0063] Polyvinyl acetal resins are usually composed of acetal group units, hydroxyl group units, and acetyl group units, and the amount of each of these units can be measured, for example, by JIS K 6728 "Testing Method for Polyvinyl Butyral" or by nuclear magnetic resonance (NMR). When the polyvinyl acetal resin contains units other than hydroxyl group units, acetyl group units, and acetal group units, the amount of hydroxyl group units and the amount of acetyl group units are measured, and the amount of these units and the amount of units other than hydroxyl group, acetyl group, and acetal group units are subtracted from 100% to calculate the amount of remaining acetal group units.

[0064] The adhesive layer preferably contains uncrosslinked polyvinyl acetal from the viewpoint of easily obtaining good film-forming properties, but may also contain crosslinked polyvinyl acetal. For example, the crosslinking method may involve thermal self-crosslinking with a carboxyl group-containing polyvinyl acetal, or intermolecular crosslinking with polyaldehyde, glyoxylic acid, or the like.

[0065] The viscosity of the polyvinyl acetal resin can be appropriately adjusted to form an adhesive layer, but in particular, when forming the above-mentioned adhesive layer (1), the viscosity of a 10% by mass toluene / ethanol=1 / 1 (mass ratio) solution of the polyvinyl acetal resin measured at 20°C and 30 rpm using a Brookfield type (B type) viscometer may be 100 to 1000 mPa·s, preferably 120 to 800 mPa·s, more preferably 150 to 600 mPa·s, even more preferably 180 to 500 mPa·s, and particularly preferably 200 to 400 mPa·s. By using a polyvinyl acetal resin having a viscosity in the above range, when bonding to a glass substrate by heat and pressure bonding, the heating temperature or heating time can be easily set to a desired range, and unmelted parts of the polyvinyl acetal resin can be made less likely to remain. In addition, even if the antenna system is exposed to high temperatures, the arrangement of the high-frequency antenna circuit board can be prevented from shifting. The viscosity of the polyvinyl acetal resin can be adjusted by using or combining a polyvinyl acetal resin produced using a polyvinyl alcohol resin having a high or low viscosity average polymerization degree as a raw material or as a part of the raw material. When the polyvinyl acetal resin used to form the adhesive layer is a mixture of multiple resins, the viscosity is the viscosity of such a mixture.

[0066] The polyvinyl acetal resin may be combined with a known or commonly used plasticizer as necessary. Examples of the plasticizer include the following plasticizers. These plasticizers may be used alone or in combination of two or more.

[0067] · Esters of polyfunctional aliphatic or aromatic acids. Examples of the ester include dialkyl adipates (e.g., dihexyl adipate, di-2-ethylbutyl adipate, dioctyl adipate, di-2-ethylhexyl adipate, hexylcyclohexyl adipate, a mixture of heptyl adipate and nonyl adipate, diisononyl adipate, heptylnonyl adipate); esters of adipic acid and an alicyclic ester alcohol or an alcohol containing an ether compound (e.g., di(butoxyethyl) adipate, di(butoxyethoxyethyl) adipate); dialkyl sebacates (e.g., dibutyl sebacate); esters of sebacic acid and an alicyclic or an alcohol containing an ether compound; esters of phthalic acid (e.g., butyl benzyl phthalate, bis-2-butoxyethyl phthalate); and esters of alicyclic polyvalent carboxylic acids and aliphatic alcohols (e.g., 1,2-cyclohexanedicarboxylic acid diisononyl ester). Esters or ethers of polyhydric aliphatic or aromatic alcohols or oligoether glycols having one or more aliphatic or aromatic substituents. Examples include esters of glycerin, diglycol, triglycol, tetraglycol, etc. with linear or branched aliphatic or alicyclic carboxylic acids. Specific examples include diethylene glycol bis-(2-ethylhexanoate), triethylene glycol bis-(2-ethylhexanoate), triethylene glycol bis-(2-ethylbutanoate), tetraethylene glycol bis-n-heptanoate, triethylene glycol bis-n-heptanoate, triethylene glycol bis-n-hexanoate, tetraethylene glycol dimethyl ether, and dipropylene glycol benzoate. Phosphate esters of aliphatic or aromatic ester alcohols, such as tris(2-ethylhexyl) phosphate (TOF), triethyl phosphate, diphenyl-2-ethylhexyl phosphate, and tricresyl phosphate. Esters of citric acid, succinic acid and / or fumaric acid.

[0068] In addition, polyesters or oligoesters composed of polyhydric alcohols and polycarboxylic acids, terminal esterified or etherified products thereof, polyesters or oligoesters composed of lactones or hydroxycarboxylic acids, or terminal esterified or etherified products thereof, etc. may be used as plasticizers.

[0069] As the plasticizer, triethylene glycol bis-(2-ethylbutanoate), triethylene glycol bis-(2-ethylhexanoate), dihexyl adipate, dibutyl sebacate, di(butoxyethyl) adipate, and di(butoxyethoxyethyl) adipate are preferred, triethylene glycol bis-(2-ethylhexanoate), di(butoxyethyl) adipate, and di(butoxyethoxyethyl) adipate are more preferred, and triethylene glycol bis-(2-ethylhexanoate) is particularly preferred.

[0070] The content of the plasticizer may be, for example, 0 to 50% by mass, preferably 0 to 40% by mass, and more preferably 0 to 30% by mass, based on the total amount of the polyvinyl acetal resin and the plasticizer.

[0071] In particular, the content of the plasticizer in the adhesive layer (1) may be 0 to 30% by mass, preferably 0 to 20% by mass, more preferably 0 to 15% by mass, even more preferably 0 to 10% by mass, and even more preferably 0 to 5% by mass, based on the total mass of the adhesive layer (1). When the content of the plasticizer in the adhesive layer is within the above range, disconnection, deformation, and displacement of the circuit of the high-frequency antenna circuit board can be suppressed when the adhesive layer is bonded to a glass substrate, and deterioration of antenna performance can be suppressed.

[0072] The content of the plasticizer in the adhesive layer (2) may be 0 to 50% by mass, preferably 20 to 35% by mass, and more preferably 25 to 30% by mass, based on the total mass of the adhesive layer (2).

[0073] A preferred polyvinyl acetal resin is commercially available, for example, from Kuraray Co., Ltd. under the name "Mobital (trademark)" and a preferred polyvinyl acetal resin film is commercially available, for example, from Kuraray Co., Ltd. under the name "Trosifol (trademark)".

[0074] (Ionomer resin) The ionomer resin is not particularly limited, but may be a thermoplastic resin having a structural unit derived from an olefin such as ethylene and a structural unit derived from an α,β-unsaturated carboxylic acid, in which at least a part of the α,β-unsaturated carboxylic acid is neutralized with a metal ion, such as an alkali metal ion such as a sodium ion, an alkaline earth metal ion such as a magnesium ion, or a zinc ion.

[0075] In the ethylene-α,β-unsaturated carboxylic acid copolymer before being neutralized with metal ions, the content of the α,β-unsaturated carboxylic acid structural unit is preferably 2% by mass or more, more preferably 5% by mass or more, based on the mass of the ethylene-α,β-unsaturated carboxylic acid copolymer, and the content of the α,β-unsaturated carboxylic acid structural unit is preferably 30% by mass or less, more preferably 20% by mass or less.

[0076] Examples of structural units derived from α,β-unsaturated carboxylic acids contained in the ionomer resin include structural units derived from acrylic acid, methacrylic acid, maleic acid, monomethyl maleate, monoethyl maleate, and maleic anhydride, and among these, structural units derived from acrylic acid or methacrylic acid are particularly preferred.

[0077] As the ionomer resin, from the viewpoint of availability, an ionomer of an ethylene-acrylic acid copolymer and an ionomer of an ethylene-methacrylic acid copolymer are more preferable, and a zinc ionomer of an ethylene-acrylic acid copolymer, a sodium ionomer of an ethylene-acrylic acid copolymer, a zinc ionomer of an ethylene-methacrylic acid copolymer, and a sodium ionomer of an ethylene-methacrylic acid copolymer are particularly preferable. The ionomer resins can be used alone or in combination of two or more kinds. A preferred film made of ionomer resin is commercially available from Kuraray Co., Ltd. under the name "Sentryglass (trademark)".

[0078] The adhesive layer may contain known or conventional additives as necessary. Examples of additives include solvents, plasticizers, ultraviolet absorbers, antioxidants, adhesion regulators, brighteners or fluorescent brighteners, stabilizers, dyes, processing aids, organic or inorganic nanoparticles, calcined silicic acid, and surfactants. The additives may be used alone or in combination.

[0079] (High frequency antenna circuit board) The high-frequency antenna circuit board includes at least one circuit layer and at least one high-frequency insulating layer, and its form is not particularly limited, and it can be used as various high-frequency circuit boards by known or conventional means.

[0080] The high frequency antenna circuit board used in the present invention can be effectively used in the antenna system of the present invention due to the high frequency characteristics derived from the high frequency insulating layer.

[0081] The circuit layer may be formed, for example, from at least a metal having electrical conductivity, and the circuit may be formed by using a known circuit processing method. The conductor forming the circuit layer may be any of various metals having electrical conductivity, such as gold, silver, copper, iron, nickel, aluminum, or alloy metals thereof.

[0082] Furthermore, the high frequency antenna circuit board may include a conductor layer such as a ground layer in addition to the circuit layer. The conductor layer may be made of various metals having electrical conductivity, such as gold, silver, copper, iron, nickel, aluminum, or alloy metals thereof. The conductors constituting the circuit layer and the conductor layer may be the same or different.

[0083] The high frequency antenna circuit board may be used for various types of transmission lines, for example, known or common transmission lines such as coaxial lines, strip lines, microstrip lines, coplanar lines, parallel lines, etc., or may be used for antennas (for example, microwave or millimeter wave antennas). The circuit board may also be used for an antenna device in which an antenna and a transmission line are integrated.

[0084] The antenna structure may have any known or conventional structure as long as it uses a high-frequency insulating layer, and examples of such antennas include antennas that utilize millimeter waves or microwaves, such as a waveguide slot antenna, a horn antenna, a lens antenna, a chip antenna, a pattern antenna, a print antenna, a triplate antenna, a microstrip antenna, and a patch antenna. The high-frequency antenna circuit board (or a semiconductor element mounting board) may be used in various sensors, particularly in vehicle-mounted radar.

[0085] The high frequency antenna circuit board may be a multi-layer circuit board having multiple circuit layers and / or conductor layers, or may be a circuit board (or a semiconductor device mounting board) on which a semiconductor device (e.g., an IC chip) is mounted.

[0086] The radio frequency antenna circuit board may be capable of supporting data transmission speeds of 10 gigabits per second or more. For example, the radio frequency antenna circuit board may be a circuit board compatible with 5G and next generation.

[0087] (High frequency insulation layer) The high-frequency antenna circuit board includes a high-frequency insulating layer. The high-frequency insulating layer is not particularly limited as long as it is an insulating layer capable of reducing the transmission loss of an electric signal in a high-frequency circuit, and examples thereof include insulating layers made of heat-resistant resins such as thermoplastic liquid crystal polymer (LCP), polyimide (PI) (particularly modified polyimide (MPI)), polyethylene naphthalate (PEN), polyether ether ketone (PEEK), polyphenylene ether (PPE), and fluororesin (e.g., polytetrafluoroethylene), and ceramics. Among these, an insulating layer made of polyimide is preferably used because it has excellent heat resistance and chemical resistance. In addition, a thermoplastic liquid crystal polymer is preferably used because of its excellent dielectric properties.

[0088] For example, the insulating layer may be formed from a thermoplastic liquid crystal polymer film or a polyimide film. In this case, a circuit layer or the like can be provided on the thermoplastic liquid crystal polymer film or the polyimide film to obtain a high frequency antenna circuit board.

[0089] The dielectric constant εp in both one direction and the direction perpendicular thereto in the plane of the high-frequency insulating layer may be, for example, 2.0 to 4.0, preferably 2.2 to 3.5, and more preferably 2.4 to 3.0 at a frequency of 28 GHz. Furthermore, the dielectric constant εf of the adhesive layer and the dielectric constant εp of the high-frequency insulating layer may be εf / εp=30 / 70 to 60 / 40, preferably 35 / 65 to 60 / 40, and more preferably 38 / 62 to 55 / 45.

[0090] The dielectric loss tangent tanδp in both one direction and the direction perpendicular thereto in the plane of the high-frequency insulating layer may be, for example, 0.010 or less, preferably 0.005 or less, and more preferably 0.003 or less at a frequency of 28 GHz. Here, the dielectric properties are values ​​measured by the above-mentioned method.

[0091] The higher of the melting point or the glass transition temperature of the high frequency insulation layer may be 150°C or higher, preferably 200°C or higher, more preferably 250°C or higher, and even more preferably 270°C or higher.

[0092] The thickness dp of the insulating layer in the high frequency antenna circuit board can be appropriately set according to the required antenna performance, and can be selected from a wide range of, for example, 10 μm to 2.5 mm, and may be, for example, about 0.1 to 2.5 mm, preferably about 0.3 to 2.0 mm, and more preferably about 0.3 to 1.0 mm. Note that, when the high frequency antenna circuit board is a multilayer circuit board, the thickness dp of the insulating layer indicates the total thickness of all the insulating layers.

[0093] From the viewpoint of excellent dielectric properties, an insulating layer made of a thermoplastic liquid crystal polymer (hereinafter, sometimes referred to as a thermoplastic liquid crystal polymer insulating layer) is preferable. The thermoplastic liquid crystal polymer film used in the thermoplastic liquid crystal polymer insulating layer is formed from a liquid crystal polymer that can be melt-formed. This thermoplastic liquid crystal polymer is a polymer that can form an optically anisotropic molten phase, and as long as it is a liquid crystal polymer that can be melt-formed, its chemical composition is not particularly limited, but examples thereof include thermoplastic liquid crystal polyester, or thermoplastic liquid crystal polyester amide in which an amide bond is introduced therein.

[0094] The thermoplastic liquid crystal polymer may be a polymer in which an imide bond, a carbonate bond, a carbodiimide bond, or a bond derived from an isocyanate such as an isocyanurate bond is further introduced into an aromatic polyester or an aromatic polyester amide.

[0095] Specific examples of the thermoplastic liquid crystal polymer used in the present invention include known thermoplastic liquid crystal polyesters and thermoplastic liquid crystal polyesteramides derived from the compounds classified into (1) to (4) below and their derivatives. However, it goes without saying that there is an appropriate range for the combination of various raw material compounds in order to form a polymer capable of forming an optically anisotropic molten phase.

[0096] (1) Aromatic or aliphatic diols (see Table 1 for representative examples) [Table 1]

[0097] (2) Aromatic or aliphatic dicarboxylic acids (see Table 2 for representative examples) [Table 2]

[0098] (3) Aromatic hydroxycarboxylic acids (see Table 3 for representative examples) [Table 3]

[0099] (4) Aromatic diamines, aromatic hydroxyamines, or aromatic aminocarboxylic acids (see Table 4 for representative examples) [Table 4]

[0100] Representative examples of thermoplastic liquid crystal polymers obtained from these raw material compounds include copolymers having the structural units shown in Tables 5 and 6.

[0101] [Table 5]

[0102] [Table 6]

[0103] Among these copolymers, polymers containing at least p-hydroxybenzoic acid and / or 6-hydroxy-2-naphthoic acid as repeating units are preferred, and in particular, (i) polymers containing repeating units of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, or (ii) copolymers containing repeating units of at least one aromatic hydroxycarboxylic acid selected from the group consisting of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, at least one aromatic diol and / or aromatic hydroxyamine, and at least one aromatic dicarboxylic acid are preferred.

[0104] For example, in the case of polymer (i), when the thermoplastic liquid crystal polymer contains at least repeating units of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, the molar ratio (A) / (B) of the p-hydroxybenzoic acid in the repeating unit (A) to the 6-hydroxy-2-naphthoic acid in the repeating unit (B) in the thermoplastic liquid crystal polymer is preferably about (A) / (B)=10 / 90 to 90 / 10, more preferably about (A) / (B)=15 / 85 to 85 / 15, and even more preferably about (A) / (B)=20 / 80 to 80 / 20.

[0105] In the case of the polymer (ii), at least one aromatic hydroxycarboxylic acid (C) selected from the group consisting of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, at least one aromatic diol (D) selected from the group consisting of 4,4'-dihydroxybiphenyl, hydroquinone, phenylhydroquinone, and 4,4'-dihydroxydiphenyl ether, and at least one aromatic dicarbohydrate (E) selected from the group consisting of terephthalic acid, isophthalic acid, and 2,6-naphthalenedicarboxylic acid are mixed. The molar ratio of each repeating unit of the aromatic hydroxycarboxylic acid (C): the aromatic diol (D): the aromatic dicarboxylic acid (E) in the thermoplastic liquid crystal polymer may be about (30-80): (35-10): (35-10), more preferably about (C): (D): (E) = (35-75): (32.5-12.5): (32.5-12.5), and even more preferably about (C): (D): (E) = (40-70): (30-15): (30-15).

[0106] The molar ratio of repeating units derived from 6-hydroxy-2-naphthoic acid in the aromatic hydroxycarboxylic acid (C) may be, for example, 85 mol% or more, preferably 90 mol% or more, more preferably 95 mol% or more. The molar ratio of repeating units derived from 2,6-naphthalenedicarboxylic acid in the aromatic dicarboxylic acid (E) may be, for example, 85 mol% or more, preferably 90 mol% or more, more preferably 95 mol% or more.

[0107] The aromatic diol (D) may be repeating units (D1) and (D2) derived from two different aromatic diols selected from the group consisting of hydroquinone, 4,4'-dihydroxybiphenyl, phenylhydroquinone, and 4,4'-dihydroxydiphenyl ether. In this case, the molar ratio of the two aromatic diols (D1) / (D2) may be 23 / 77 to 77 / 23, more preferably 25 / 75 to 75 / 25, and even more preferably 30 / 70 to 70 / 30.

[0108] The molar ratio of the repeating structural units derived from the aromatic diol (D) to the repeating structural units derived from the aromatic dicarboxylic acid (E) is preferably (D) / (E)=95 / 100 to 100 / 95. If it is outside this range, the degree of polymerization does not increase and the mechanical strength tends to decrease.

[0109] The ability to form an optically anisotropic molten phase in the present invention can be confirmed, for example, by placing a sample on a hot stage, heating it in a nitrogen atmosphere, and observing the light transmitted through the sample.

[0110] The preferred thermoplastic liquid crystal polymer may have a melting point (hereinafter referred to as Tm0) in the range of 200 to 360°C, preferably in the range of 240 to 360°C, more preferably in the range of 260 to 360°C, and even more preferably in the range of 270 to 350°C. Tm0 is determined by measuring the temperature at which the main endothermic peak appears using a differential scanning calorimeter (Shimadzu Corporation DSC). That is, the thermoplastic liquid crystal polymer sample is heated at a rate of 10°C / min to completely melt it, and then the melt is cooled to 50°C at a rate of 10°C / min, and the position of the endothermic peak that appears after heating again at a rate of 10°C / min is determined as the melting point of the thermoplastic liquid crystal polymer sample.

[0111] Thermoplastic polymers such as polyethylene terephthalate, modified polyethylene terephthalate, polyolefin, polycarbonate, polyarylate, polyamide, polyphenylene sulfide, polyether ether ketone, and fluororesin, various additives, fillers, and the like may be added to the thermoplastic liquid crystal polymer within a range that does not impair the effects of the present invention.

[0112] The thermoplastic liquid crystal polymer film is obtained, for example, by extrusion molding the melt kneaded product of the thermoplastic liquid crystal polymer. Any method can be used as the extrusion molding method, but the well-known T-die method, inflation method, etc. are industrially advantageous. In particular, in the inflation method, stress is applied not only in the mechanical axis direction (hereinafter abbreviated as MD) of the thermoplastic liquid crystal polymer film, but also in the direction perpendicular thereto (hereinafter abbreviated as TD), and the film can be uniformly stretched in the MD and TD directions, so that a thermoplastic liquid crystal polymer film with controlled molecular orientation, dielectric properties, etc. in the MD and TD directions can be obtained.

[0113] If necessary, a known or conventional heat treatment may be performed to adjust the melting point and / or thermal expansion coefficient of the thermoplastic liquid crystal polymer film. The heat treatment conditions can be appropriately set according to the purpose, and for example, the melting point (Tm) of the thermoplastic liquid crystal polymer film may be increased by heating for several hours at a temperature equal to or higher than the melting point (Tm0)-10°C (for example, about Tm0-10°C to Tm0+30°C, preferably about Tm0°C to Tm0+20°C).

[0114] By providing a circuit layer and / or a conductor layer on the obtained thermoplastic liquid crystal polymer film by a known or conventional method, it is possible to produce a high frequency antenna circuit board having a thermoplastic liquid crystal polymer insulating layer.

[0115] The melting point (Tm) of the thermoplastic liquid crystal polymer insulating layer may be, for example, 200 to 380°C, and preferably in the range of 240 to 370°C. The melting point (Tm) of the thermoplastic liquid crystal polymer insulating layer can be obtained by observing the thermal behavior of a sample obtained from the thermoplastic liquid crystal polymer insulating layer (or thermoplastic liquid crystal polymer film) using a differential scanning calorimeter. That is, the position of the endothermic peak that appears when the temperature of the thermoplastic liquid crystal polymer film sample is raised at a rate of 10°C / min can be determined as the melting point (Tm) of the thermoplastic liquid crystal polymer film.

[0116] The thermoplastic liquid crystal polymer insulating layer may have, for example, a thermal expansion coefficient of 0 to 25 ppm / ° C., and the thermal expansion coefficient may preferably be about 5 to 22 ppm / ° C. The thermal expansion coefficient can be understood as a value measured using a thermomechanical analyzer (TMA) between 30° C. and 150° C. when the temperature is raised from 25° C. to 200° C. at a rate of 5° C. / min, cooled to 30° C. at a rate of 20° C. / min, and then raised again at a rate of 5° C. / min.

[0117] From the viewpoint of excellent heat resistance, an insulating layer made of polyimide (hereinafter, sometimes referred to as a polyimide insulating layer) is preferable. The polyimide is not particularly limited as long as it is a polymer having an imide group in a structural unit, and examples thereof include polyimide-based resins such as polyimide, polyamideimide, polybenzimidazole, polyimide ester, polyetherimide, and polysiloxaneimide.

[0118] Polyimide can be formed by imidizing (curing) a precursor polyamic acid. Polyamic acid can be synthesized by reacting a known diamine with a tetracarboxylic acid (including its acid anhydride) in the presence of a solvent. As the diamine, an aromatic diamine, an aliphatic diamine, an alicyclic diamine, etc. can be used, and from the viewpoint of heat resistance, an aromatic diamine is preferable. As the aromatic diamine, for example, 4,4'-diaminodiphenyl ether, 2'-methoxy-4,4'-diaminobenzanilide, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxy-4,4'-diaminobiphenyl, 4,4'-diaminobenzanilide, 5-amino-2-(p-aminophenyl)benzoxazole, etc. can be mentioned. As the tetracarboxylic acid, an aromatic tetracarboxylic acid, an aliphatic tetracarboxylic acid, an alicyclic tetracarboxylic acid, an anhydride thereof, etc. can be used, and from the viewpoint of heat resistance, an aromatic tetracarboxylic acid anhydride is preferable. As the aromatic tetracarboxylic acid anhydride, for example, pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic acid dianhydride, 4,4'-oxydiphthalic anhydride, etc. can be mentioned. Each of these diamines and tetracarboxylic acids can be used alone or in combination of two or more kinds.

[0119] The polyimide film used in the polyimide insulating layer can be produced, for example, by applying a solution of polyamic acid (polyimide precursor) obtained by reacting diamine with tetracarboxylic acid to a support, drying the solution to obtain a polyamic acid film, and then heat-treating the film to harden (imidize). The polyamic acid solution can be applied by known application methods such as spin coating, comma coater, screen printing, slit coating, roll coating, knife coating, dip coating, and die coating.

[0120] Various additives, fillers, etc. may be added to the polyimide film within the range that does not impair the effects of the present invention.

[0121] Polyimide films are commercially available, for example, under the trade names Kapton EN, Kapton H, and Kapton V manufactured by DuPont-Toray Co., Ltd., Apical NPI (trade name) manufactured by Kaneka Corporation, and Upilex S (trade name) manufactured by Ube Industries, Ltd.

[0122] (protective layer) The protective layer may be disposed adjacent to the radio frequency antenna circuit board and / or the adhesive layer. The protective layer may protect the radio frequency antenna circuit board and / or the adhesive layer from water, moisture, scratches, dust, and the like before and after the formation of the antenna system. The protective layer may be directly attached to the radio frequency antenna circuit board and / or the adhesive layer, or may be attached via other fixing means (not shown). For example, by disposing the protective layer in this manner, it is possible to protect the radio frequency antenna circuit board and / or the adhesive layer in the laminate before the formation of the antenna system, and in the antenna system formed by adhering to a glass substrate.

[0123] The protective layer may also be peelable from an adjacent layer, for example, in a laminate in which the protective layer is adjacent to an adhesive layer, the adhesive layer may be protected by the protective layer prior to forming the antenna system, and the protective layer may be peeled away from the adhesive layer to expose the adhesive layer adjacent to a glass substrate for adhering to form the antenna system.

[0124] The protective layer is not particularly limited as long as it can protect the adhesive layer and the high frequency antenna circuit board, and can be selected from various inorganic materials and organic materials according to the object to be protected and the purpose of protection. Preferred protective materials include glass and polyester resin. Examples of glass include glass substrates described later. Examples of polyester resins include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), and the like. Other examples include organic material films such as acrylic films. The protective layer may be subjected to various surface treatments by known or conventional methods to improve adhesion or to make it peelable, as necessary.

[0125] As described above, the laminate of the present invention may be applied to the adhesive layer with a glass substrate or the like as an adherend, or may be applied with a substrate other than a glass substrate. The adherend may be of various forms, such as a glass substrate, a wall of a building, or a side of a vehicle. The laminate of the present invention can form an antenna system by applying the high-frequency antenna circuit board to various adherends. In addition, the laminate may be applied to an adherend other than a glass substrate constituting the first glass layer described later via another fixing means (e.g., a pressure-sensitive adhesive, etc.) without the adhesive layer to form an antenna system.

[0126] The thickness dc of the protective layer may be 0.01 to 2 mm, preferably 0.02 to 1.5 mm, more preferably 0.03 to 1 mm, and particularly preferably 0.03 to 0.5 mm, from the viewpoint of thinning the antenna system while protecting the adhesive layer and the high-frequency antenna circuit board.

[0127] <Antenna system> The antenna system of the present invention comprises at least a high frequency antenna circuit board, an adhesive layer adjacent to at least one surface of the high frequency antenna circuit board and made of at least one resin selected from the group consisting of polyvinyl acetal resin and ionomer resin, and a first glass layer adjacent to the adhesive layer and having a higher dielectric constant than the adhesive layer. In the antenna system of the present invention, the first glass layer transmits high frequency waves, the adhesive layer transmits high frequency waves incident from the first glass layer, and the high frequency waves incident from the adhesive layer are received by the high frequency antenna circuit board.

[0128] The high frequency that is the target of the antenna system of the present invention may be, for example, 1 GHz or higher, preferably 2 GHz or higher, more preferably 6 GHz or higher, further preferably 30 GHz or higher, and particularly preferably 50 GHz or higher. The upper limit of the frequency is not particularly limited, but may be, for example, 400 GHz or lower, preferably 300 GHz or lower.

[0129] Hereinafter, specific embodiments of the antenna system of the present invention will be described with reference to the drawings, but the antenna system of the present invention is not limited to the exemplified embodiments.

[0130] [Fifth embodiment] Fig. 5 is a schematic cross-sectional view for explaining an antenna system according to a fifth embodiment. As shown in Fig. 5, an antenna system 100 according to the fifth embodiment includes a first glass layer 101, an adhesive layer 103 having a lower dielectric constant than the first glass layer 101, and a high-frequency antenna circuit board 107. The first glass layer 101 and the adhesive layer 103 have adjacent portions in the thickness direction, and the adhesive layer 103 and the high-frequency antenna circuit board 107 have adjacent portions in the thickness direction. The first glass layer 101 may be, for example, a window glass. The position of the high frequency antenna circuit board within the surface of the window glass is not particularly limited, and may be disposed so that one end of the high frequency antenna circuit board 107 contacts the end of the window glass, as shown in FIG. 5, or may be disposed so that the end of the high frequency antenna circuit board 107 is located inward (for example, about 1 to 10 cm inward) from the end of at least one side of the window glass. For example, when visibility is required as in window glass or automobile windshield, it is preferable to dispose the high frequency antenna circuit board 107 in a portion that does not obstruct visibility. For example, the antenna circuit in the high frequency antenna circuit board 107 may be disposed in an area 0 cm to 10 cm inward from the end of at least one side of the first glass layer 103. Furthermore, in order to prevent rust or the like caused by absorption of water from the end, the antenna circuit in high frequency antenna circuit board 107 may be disposed away from the end of first glass layer 103, for example, in an area 1 cm or more inward (preferably an area 1 cm to 10 cm inward) from the end of at least one side of first glass layer 103. The same applies to the following embodiments.

[0131] 5, high frequency wave A, indicated by an arrow with one end pointing toward first glass layer 101, enters first glass layer 101 from the outside of first glass layer 101 and exits to the inside. Therefore, in thickness direction Z indicated by double-ended arrows, first glass layer 101 has one side as an outer surface and the other as an inner surface. Adhesive layer 103 is adjacent to the inside of first glass layer 101 in thickness direction Z, and high frequency antenna circuit board 107 is adjacent to the inside of adhesive layer 103 in thickness direction Z.

[0132] After being incident on the outer surface of the first glass layer 101, the high frequency wave A reaches the high frequency antenna circuit board 107 via the adhesive layer 103 adjacent to the first glass layer 101. Then, the high frequency wave A that reaches the high frequency antenna circuit board 107 is received by the high frequency antenna circuit board 107. Note that even in the embodiments described in this specification regarding only reception, not only reception but also transmission is possible, and this is the same in all the embodiments.

[0133] The high frequency antenna circuit board 107 includes a high frequency insulating layer (hereinafter, may be simply referred to as an insulating layer) 105, a circuit layer 104 disposed on one surface (outer surface in the thickness direction Z) of the insulating layer 105, and a conductor layer 106 disposed on the other surface (inner surface in the thickness direction Z) of the insulating layer 105. Although only one circuit layer is shown in FIG. 5 for simplification, the high frequency antenna circuit board 107 may be a multi-layer circuit board since the insulating layer may include an inner layer circuit not shown. Furthermore, the conductor layer 106 may have a circuit pattern as necessary, or may be a metal layer having reflectivity. When the high frequency wave A incident on the high frequency antenna circuit board 107 is reflected by the metal layer having reflectivity in the conductor layer 106, the utilization efficiency of the high frequency wave A in the high frequency antenna circuit board 107 can be improved.

[0134] High frequency wave A has a wavelength λ at a predetermined frequency, and after entering first glass layer 101, a portion of the wave is reflected without reaching high frequency antenna circuit board 107. However, by using adhesive layer 103 composed of at least one type selected from the group consisting of polyvinyl acetal resin and ionomer resin, and making the dielectric constant εf of adhesive layer 103 smaller than the dielectric constant εg of first glass layer 101, it is possible to reduce the reflectance R of high frequency wave A from when it enters first glass layer 101 to when it reaches the surface of high frequency antenna circuit board 107, and to increase the proportion of high frequency wave A that reaches high frequency antenna circuit board 107.

[0135] In the antenna system 100, in the thickness direction Z, the first glass layer 101 has a thickness dg, the adhesive layer 103 has a thickness df on the radio frequency antenna circuit board 107, and the insulating layer 105 in the radio frequency antenna circuit board 107 has a thickness dp. Here, the thickness df of the adhesive layer 103 on the radio frequency antenna circuit board 107 is understood as the distance between the first glass layer 101 and the insulating layer 105. Note that the total thickness da of the adhesive layer 103 indicates the same thickness as the thickness df on the radio frequency antenna circuit board 107.

[0136] The thickness dg of the first glass layer 101 can be appropriately set, for example, within the range of 0.1 to 100 mm depending on the application of the object to which the first glass layer is provided, and may be, for example, 0.5 to 20 mm (for example, about 1 to 20 mm), preferably 1 to 15 mm (for example, about 3 to 13 mm), and more preferably 1.5 to 10 mm (for example, about 4 to 10 mm). For example, the first glass layer 101 may be a first glass layer of a vehicle or a first glass layer of a building, or may be a first glass layer that forms laminated glass.

[0137] The thickness dp of the insulating layer 105 in the high-frequency antenna circuit board 107 can be set appropriately depending on the required antenna performance, etc., and can be selected from a wide range of, for example, 10 μm to 2.5 mm, and may be, for example, about 0.1 to 2.5 mm, preferably about 0.3 to 2.0 mm, and more preferably about 0.3 to 1.0 mm.

[0138] 5, the adhesive layer 103 has adhesiveness to both the first glass layer 101 and the radio frequency antenna circuit board 107, and the radio frequency antenna circuit board 107 is attached to the first glass layer 101 via the adhesive layer 103. Therefore, the adhesive layer 103 has a surface in close contact with the first glass layer 101, and the radio frequency antenna circuit board 107 has a surface in close contact with the adhesive layer 103.

[0139] For example, when the adhesive layer 103 does not have adhesiveness to the high-frequency antenna circuit board 107, the first glass layer 101, the adhesive layer 103, and the high-frequency antenna circuit board 107 may be adjacent to each other using an external fixing means as necessary. In this case, it is preferable that the adjacent surfaces between the adhesive layer 103 and the high-frequency antenna circuit board 107 are in contact with each other without an air gap therebetween.

[0140] In the first glass layer 101, the high frequency antenna circuit board 107 can be disposed in a desired location and with a desired size depending on the application.

[0141] If necessary, a protective member for protecting the high-frequency antenna circuit board 107 may be provided on the back surface (i.e., the surface opposite to the surface in contact with the adhesive layer 103) and / or the side surface of the high-frequency antenna circuit board 107, which is the same in the following embodiments.

[0142] When the antenna system 100 is used for a windshield of an automobile or the like, a sealant may be provided on at least a part of the edge of the first glass layer 103. The same applies to the following embodiments.

[0143] [Sixth embodiment] FIG. 6 is a schematic cross-sectional view for explaining an antenna system according to a sixth embodiment. As shown in FIG. 6, an antenna system 200 according to the sixth embodiment includes a first glass layer 201, an adhesive layer 203 having a lower dielectric constant than the first glass layer 201, a high-frequency antenna circuit board 107, and a second glass layer 202 disposed opposite the first glass layer 201 in the thickness direction Z. The same components as those in the fifth embodiment are denoted by the same reference numerals, and their description will be omitted. The antenna system 200 may be, for example, a window glass made of laminated glass formed by the first glass layer 201 and the second glass layer 202, or may be in a state in which the high-frequency antenna circuit board 107 is disposed inside the first glass layer 201 and the second glass layer 202 via the adhesive layer 203.

[0144] In the sixth embodiment, the high frequency antenna circuit board 107 is embedded in the adhesive layer 203, and the first glass layer 201 and the second glass layer 202 are bonded together by the adhesive layer 203.

[0145] High frequency wave A has a wavelength λ at a predetermined frequency. After entering the first glass layer 201, a portion of the wave does not reach the high frequency antenna circuit board 107 and is reflected at a predetermined reflectance R. However, by using an adhesive layer 203 composed of at least one resin selected from the group consisting of polyvinyl acetal resin and ionomer resin, the dielectric constant εf of the adhesive layer 203 is made smaller than the dielectric constant εg of the first glass layer 201, thereby reducing the reflectance R and improving the proportion of high frequency wave A that reaches the high frequency antenna circuit board 107.

[0146] In the antenna system 200, in the thickness direction Z, the first glass layer 201 has a thickness dg, the adhesive layer 203 has a thickness df on the radio frequency antenna circuit board 107, and the insulating layer 105 in the radio frequency antenna circuit board 107 has a thickness dp. Here, the thickness df of the adhesive layer 203 on the radio frequency antenna circuit board 107 is understood as the distance between the first glass layer 201 and the insulating layer 105. Note that the total thickness da of the adhesive layer 203 indicates the distance between the first glass layer 201 and the second glass layer 202.

[0147] The thickness dg of the first glass layer 201 can be set appropriately depending on the use of the object to which the first glass layer 201 is attached, and may be, for example, 0.5 to 20 mm (e.g., about 1 to 20 mm), preferably 1 to 15 mm (e.g., about 3 to 13 mm), and more preferably 1.5 to 10 mm (e.g., about 4 to 10 mm).

[0148] The thickness dg' of the second glass layer 202 can also be appropriately set depending on the use of the object to which the second glass layer 202 is attached, and may be, for example, 0.5 to 20 mm (e.g., about 1 to 20 mm), preferably 1 to 15 mm (e.g., about 3 to 13 mm), and more preferably 1.5 to 10 mm (e.g., about 4 to 10 mm).

[0149] In the first glass layer 201, the high frequency antenna circuit board 107 can be disposed in a desired location and with a desired size depending on the application.

[0150] [Seventh embodiment] Fig. 7 is a schematic cross-sectional view for explaining an antenna system according to a seventh embodiment. As shown in Fig. 7, an antenna system 300 according to the seventh embodiment includes a first glass layer 301, an adhesive layer 303 having a lower dielectric constant than the first glass layer 301, a high-frequency antenna circuit board 107, and a second glass layer 302. Note that the same components as those in the first embodiment are denoted by the same reference numerals, and the description thereof will be omitted. The first glass layer 301 and the adhesive layer 303 have portions adjacent to each other in the thickness direction, and the adhesive layer 303 and the high frequency antenna circuit board 107 have portions adjacent to each other in the thickness direction. Furthermore, the high frequency antenna circuit board 107 may be attached to the second glass layer 302 by various fastening means. For example, the high frequency antenna circuit board 107 may be attached to the second glass layer 302 via a fixing means 308.

[0151] In this embodiment, the second glass layer 302 may be, for example, a window glass, and the high frequency antenna circuit board 107 may be disposed on the outside of the window glass.

[0152] In the seventh embodiment, after the high frequency wave A enters the first glass layer 301, a portion of the high frequency wave A is reflected by a predetermined reflectance R without reaching the high frequency antenna circuit board 107. However, by using an adhesive layer 303 composed of at least one resin selected from the group consisting of polyvinyl acetal resin and ionomer resin, the dielectric constant εf of the adhesive layer 303 is made smaller than the dielectric constant εg of the first glass layer 301, thereby reducing the reflectance R and improving the proportion of the high frequency wave A that reaches the high frequency antenna circuit board 107.

[0153] In the antenna system 300, in the thickness direction Z, the first glass layer 301 has a thickness dg, the adhesive layer 303 has a thickness df on the radio frequency antenna circuit board 107, and the insulating layer 105 in the radio frequency antenna circuit board 107 has a thickness dp. Here, the thickness df of the adhesive layer 303 is understood as the distance between the first glass layer 301 and the insulating layer 305, not the distance between the first glass layer 301 and the second glass layer 302. Note that the total thickness da of the adhesive layer 303 indicates the same thickness as the thickness df on the radio frequency antenna circuit board 107.

[0154] The first glass layer 301 may be thin from the viewpoint of weight reduction, and the thickness dg may be, for example, about 0.5 to 7 mm, preferably about 0.7 to 5 mm, and more preferably about 0.8 to 3 mm.

[0155] The thickness dg' of the second glass layer 302 can be set appropriately depending on the use of the object to which the second glass layer 302 is attached, and may be, for example, 0.5 to 20 mm (e.g., about 1 to 20 mm), preferably 1 to 15 mm (e.g., about 3 to 13 mm), and more preferably 1.5 to 10 mm (e.g., about 4 to 10 mm).

[0156] When the fixing means 308 is provided, the fixing means 308 can be made of a known or commonly used adhesive material having adhesiveness to the radio frequency antenna circuit board and glass, as long as the fixing means 308 can adhere the radio frequency antenna circuit board 107 to the second glass layer. The fixing means 308 may also be at least one selected from the group consisting of polyvinyl acetal resin and ionomer resin used in adhesive layers. Alternatively, from the viewpoint of simplicity, the fixing means 308 may be a pressure-sensitive adhesive tape such as a double-sided tape.

[0157] In the second glass layer 302, the high frequency antenna circuit board 107 can be disposed in a desired location and with a desired size depending on the application.

[0158] [Eighth embodiment] Fig. 8 is a schematic cross-sectional view for explaining an antenna system according to an eighth embodiment. As shown in Fig. 8, an antenna system 400 according to the eighth embodiment includes a first glass layer 401, an adhesive layer 403 having a lower dielectric constant than the first glass layer 401, and a high-frequency antenna circuit board 107. Note that the same components as those in the first embodiment are denoted by the same reference numerals, and the description thereof will be omitted.

[0159] The first glass layer 401 and the adhesive layer 403 have a portion adjacent to each other in the thickness direction, and the adhesive layer 403 and the high-frequency antenna circuit board 107 have a portion adjacent to each other in the thickness direction.

[0160] In this embodiment, the adherend 409 may be of various forms as long as it can fix the high frequency antenna circuit board 107, and may be, for example, a wall of a building or a side of a vehicle. The adherend 409 may also be a flexible material such as a PEN film, a PET film, or an acrylic film.

[0161] In the eighth embodiment, after the high frequency wave A enters the first glass layer 401, a part of the high frequency wave A is reflected by a predetermined reflectance R without reaching the high frequency antenna circuit board 107. However, by using an adhesive layer 403 composed of at least one kind selected from the group consisting of polyvinyl acetal resin and ionomer resin, and making the dielectric constant εf of the adhesive layer 403 smaller than the dielectric constant εg of the first glass layer 401, it is possible to reduce the reflectance R and improve the proportion of the high frequency wave A that reaches the high frequency antenna circuit board 107.

[0162] In the antenna system 400, in the thickness direction Z, the first glass layer 401 has a thickness dg, the adhesive layer 403 has a thickness df on the radio frequency antenna circuit board 107, and the insulating layer 105 in the radio frequency antenna circuit board 107 has a thickness dp. Here, the thickness df of the adhesive layer 403 is understood as the distance between the first glass layer 401 and the insulating layer 105. Note that the total thickness da of the adhesive layer 403 indicates the same thickness as the thickness df on the radio frequency antenna circuit board 107.

[0163] First glass layer 401 may be thin from the viewpoint of weight reduction, and the thickness dg may be, for example, about 0.5 to 7 mm, preferably about 0.7 to 5 mm, and more preferably about 0.8 to 3 mm.

[0164] Furthermore, the antenna system 400 may be attached to the substrate 409 by various fastening means. For example, the antenna system 400 may be attached to the substrate 409 using fastening means 408a and 408b that surround the sides of the antenna system 400. The fastening means 408a and 408b may be separate members or may be an integrated member. The fastening means may include bolts, screws, screws, etc.

[0165] In addition to or instead of the fixing means 408a and 408b, the high frequency antenna circuit board 107 and the adherend 409 may be adhered to each other via a fixing means such as the fixing means 308 shown in FIG. 7, although not shown.

[0166] For example, the fixing means may be a known or commonly used adhesive material having adhesive properties for the radio frequency antenna circuit board and the adherend, so long as it can adhere the radio frequency antenna circuit board 107 to the adherend 409. For example, from the viewpoint of simplicity, the fixing means may be a pressure-sensitive adhesive material such as double-sided tape.

[0167] On the adherend 409, the high frequency antenna circuit board 107 can be arranged in a desired location and with a desired size depending on the application.

[0168] [Ninth embodiment] FIG. 9 is a schematic cross-sectional view for explaining an antenna system according to a ninth embodiment. As shown in FIG. 9, an antenna system 500 according to a ninth embodiment includes a first glass layer 501, a first adhesive layer 503a having a lower dielectric constant than the first glass layer 501, a high-frequency antenna circuit board 107, a second adhesive layer 503b, and a second glass layer 502 disposed opposite the first glass layer 501 in the thickness direction Z. The same components as those in the fifth embodiment are given the same reference numerals, and their description will be omitted. The antenna system 500 may be, for example, a window glass made of laminated glass formed by the first glass layer 501 and the second glass layer 502, or may be in a state in which the high-frequency antenna circuit board 107 is disposed inside the first glass layer 501 and the second glass layer 502 via the first adhesive layer 503a and the second adhesive layer 503b.

[0169] In the ninth embodiment, the high-frequency antenna circuit board 107 is embedded at the boundary between the first adhesive layer 503a and the second adhesive layer 503b, and the first adhesive layer 503a and the second adhesive layer 503b bond the first glass layer 501 and the second glass layer 502 to form laminated glass.

[0170] High frequency A has a wavelength λ at a predetermined frequency. After entering the first glass layer 501, a portion of the radio frequency wave does not reach the radio frequency antenna circuit board 107 and is reflected at a predetermined reflectance R. However, by using a first adhesive layer 503a composed of at least one resin selected from the group consisting of polyvinyl acetal resin and ionomer resin, the dielectric constant εf of the first adhesive layer 503a is made smaller than the dielectric constant εg of the first glass layer 501, thereby reducing the reflectance R and improving the proportion of high frequency A that reaches the radio frequency antenna circuit board 107.

[0171] In the antenna system 500, in the thickness direction Z, the first glass layer 501 has a thickness dg, the first adhesive layer 503a has a thickness df on the radio frequency antenna circuit board 107, and the insulating layer 105 in the radio frequency antenna circuit board 107 has a thickness dp. Here, the thickness df of the first adhesive layer 503a on the radio frequency antenna circuit board 107 is understood as the distance between the first glass layer 501 and the insulating layer 105. Note that the total thickness da of the first adhesive layer 503a indicates the distance between the first glass layer 501 and the second adhesive layer 503b.

[0172] The thickness dg of the first glass layer 501 can be appropriately set depending on the use of the object to which the first glass layer 501 is attached, and may be, for example, about 0.5 to 20 mm, preferably about 1 to 15 mm, and more preferably about 1.5 to 10 mm.

[0173] The thickness dg' of the second glass layer 502 can also be appropriately set depending on the use of the object to which the second glass layer 502 is attached, and may be, for example, about 0.5 to 20 mm, preferably about 1 to 15 mm, and more preferably about 1.5 to 10 mm.

[0174] The total thickness da of the first adhesive layer 503a and the total thickness da' of the second adhesive layer 503b may be the same or different from each other. For example, from the viewpoint of embedding the high frequency antenna circuit board 107 and reducing the thickness of the laminated glass, either one of the total thickness da of the first adhesive layer 503a and the total thickness da' of the second adhesive layer 503b may be more than 370 μm and 2.5 mm or less, preferably 380 μm to 2.28 mm, more preferably 500 μm to 1.6 mm, and even more preferably 750 to 850 μm, and the other may be 370 μm or less, preferably 1 to 300 μm, more preferably 5 to 200 μm, even more preferably 10 to 100 μm, even more preferably 20 to 60 μm, particularly preferably 20 μm or more and less than 50 μm, particularly preferably 20 to 45 μm, and most preferably 20 to 40 μm. In this way, by providing an adhesive layer having a certain thickness, it becomes possible to embed the high-frequency antenna circuit board 107, and by making the other adhesive layer thinner, it becomes possible to make the laminated glass thinner while still maintaining adhesiveness.

[0175] In the first glass layer 501, the high frequency antenna circuit board 107 can be disposed in a desired location and with a desired size depending on the application.

[0176] [Tenth embodiment] FIG. 10 is a schematic cross-sectional view for explaining an antenna system according to a tenth embodiment. As shown in FIG. 10, an antenna system 600 according to a tenth embodiment includes a first glass layer 601, a first adhesive layer 603a having a lower dielectric constant than the first glass layer 601, a high-frequency antenna circuit board 107, a second adhesive layer 603b, and a second glass layer 602 disposed opposite the first glass layer 601 in the thickness direction Z. The same components as those in the fifth embodiment are given the same reference numerals, and their description will be omitted. The antenna system 600 may be, for example, a window glass made of laminated glass formed by the first glass layer 601 and the second glass layer 602, or may be in a state in which the high-frequency antenna circuit board 107 is disposed inside the first glass layer 601 and the second glass layer 602 via the first adhesive layer 603a and the second adhesive layer 603b.

[0177] In the tenth embodiment, the high-frequency antenna circuit board 107 is embedded in a first adhesive layer 603a together with a second adhesive layer 603b, and the first adhesive layer 603a bonds a first glass layer 601 and a second glass layer 602 together to form a laminated glass.

[0178] High frequency wave A has a wavelength λ at a predetermined frequency. After entering the first glass layer 601, a portion of the wave does not reach the high frequency antenna circuit board 107 and is reflected at a predetermined reflectance R. However, by using a first adhesive layer 603a composed of at least one resin selected from the group consisting of polyvinyl acetal resin and ionomer resin, the dielectric constant εf of the first adhesive layer 603a is made smaller than the dielectric constant εg of the first glass layer 601, thereby reducing the reflectance R and improving the proportion of high frequency wave A that reaches the high frequency antenna circuit board 107.

[0179] In the antenna system 600, the first glass layer 601 has a thickness dg in the thickness direction Z, the first adhesive layer 603a has a thickness df on the radio frequency antenna circuit board 107, and the insulating layer 105 in the radio frequency antenna circuit board 107 has a thickness dp. Here, the thickness df of the first adhesive layer 603a on the radio frequency antenna circuit board 107 is understood as the distance between the first glass layer 601 and the insulating layer 105. Note that the total thickness da of the first adhesive layer 603a indicates the distance between the first glass layer 601 and the second glass layer 602.

[0180] The thickness dg of the first glass layer 601 can be appropriately set depending on the use of the object to which the first glass layer 601 is attached, and may be, for example, about 0.5 to 20 mm, preferably about 1 to 15 mm, and more preferably about 1.5 to 10 mm.

[0181] The thickness dg' of the second glass layer 602 can also be appropriately set depending on the use of the object to which the second glass layer 602 is attached, and may be, for example, about 0.5 to 20 mm, preferably about 1 to 15 mm, and more preferably about 1.5 to 10 mm.

[0182] The total thickness da of the first adhesive layer 603a is made thicker than the total thickness da' of the second adhesive layer 603b, so that the first adhesive layer 603a can bury the high frequency antenna circuit board 107 and the second adhesive layer 603b. For example, the total thickness da of the first adhesive layer 603a may be more than 370 μm and 2.5 mm or less, preferably 380 μm to 2.28 mm, more preferably 500 μm to 1.6 mm, and even more preferably 750 to 850 μm, and the total thickness da' of the second adhesive layer 603b may be 370 μm or less, preferably 1 to 300 μm, more preferably 5 to 200 μm, even more preferably 10 to 100 μm, even more preferably 20 to 60 μm, particularly preferably 20 μm or more and less than 50 μm, particularly preferably 20 to 45 μm, and most preferably 20 to 40 μm.

[0183] In the first glass layer 601, the high frequency antenna circuit board 107 can be disposed in a desired location and with a desired size depending on the application.

[0184] [Eleventh embodiment] FIG. 11 is a schematic cross-sectional view for explaining an antenna system according to an eleventh embodiment. As shown in FIG. 11, an antenna system 700 according to an eleventh embodiment includes a first glass layer 701, a first adhesive layer 703a having a lower dielectric constant than the first glass layer 701, a high-frequency antenna circuit board 107, a second adhesive layer 703b, and a protective layer 718. The same components as those in the fifth embodiment are given the same reference numerals, and their description is omitted. The first glass layer 701 and the first adhesive layer 703a have adjacent portions in the thickness direction, the first adhesive layer 703a and the high-frequency antenna circuit board 107 have adjacent portions in the thickness direction, the high-frequency antenna circuit board 107 and the second adhesive layer 703b have adjacent portions in the thickness direction, and the second adhesive layer 703 and the protective layer 718 have adjacent portions in the thickness direction.

[0185] In the antenna system 700 according to the eleventh embodiment, the protective layer 718 is provided in the direction opposite to the incident direction of the high frequency wave A, thereby making it possible to protect the high frequency antenna circuit board 107 from water, moisture, scratches, adhesion of dust, and the like. From the viewpoint of protecting the high frequency antenna circuit board 107, the protective layer 718 may be fixed to the high frequency antenna circuit board 107 via a second adhesive layer 703b made of polyvinyl acetal resin or ionomer resin, or may be bonded via a fixing means made of a material other than polyvinyl acetal resin or ionomer resin and capable of bonding the high frequency antenna circuit board 107 and the protective layer 718, for example, the protective layer 718 may be directly bonded to the high frequency antenna circuit board 107, or the protective layer may be attached to the high frequency antenna circuit board by various fixing means.

[0186] High frequency wave A has a wavelength λ at a predetermined frequency. After entering the first glass layer 701, a portion of the wave does not reach the high frequency antenna circuit board 107 and is reflected at a predetermined reflectance R. However, by using a first adhesive layer 703a composed of at least one resin selected from the group consisting of polyvinyl acetal resin and ionomer resin, the dielectric constant εf of the first adhesive layer 703a is made smaller than the dielectric constant εg of the first glass layer 701, thereby reducing the reflectance R and improving the proportion of high frequency wave A that reaches the high frequency antenna circuit board 107.

[0187] In the antenna system 700, the first glass layer 701 has a thickness dg in the thickness direction Z, the first adhesive layer 703a has a thickness df on the radio frequency antenna circuit board 107, and the insulating layer 105 in the radio frequency antenna circuit board 107 has a thickness dp. Here, the thickness df of the first adhesive layer 703a on the radio frequency antenna circuit board 107 is understood as the distance between the first glass layer 701 and the insulating layer 105. Note that the total thickness da of the first adhesive layer 703a indicates the same thickness as the thickness df on the radio frequency antenna circuit board 107.

[0188] The thickness dg of the first glass layer 701 can be appropriately set depending on the use of the object to which the first glass layer 701 is attached, and may be, for example, about 0.5 to 20 mm, preferably about 1 to 15 mm, and more preferably about 1.5 to 10 mm.

[0189] The thickness df (or the total thickness da) of the first adhesive layer 703a on the high frequency antenna circuit board 107 and the thickness df' (or the total thickness da') of the second adhesive layer 703b on the high frequency antenna circuit board 107 may be the same as or different from each other. For example, from the viewpoint of making the antenna system 700 thinner, the thickness df (or the total thickness da) of the first adhesive layer 503a on the high frequency antenna circuit board 107 and the thickness df' (or the total thickness da') of the second adhesive layer 503b on the high frequency antenna circuit board 107 may be more than 370 μm and 2.5 mm or less, preferably 380 μm to 2.28 mm, more preferably 500 μm to 1.6 mm, and even more preferably 750 to 850 μm.

[0190] The thickness dc of the protective layer should be sufficient to protect the high-frequency antenna circuit board 107, but may be thin from the viewpoint of weight reduction, and may be, for example, about 0.01 to 7 mm, preferably about 0.1 to 5 mm, and more preferably about 0.5 to 3 mm.

[0191] In the first glass layer 701, the high frequency antenna circuit board 107 can be disposed in a desired location and with a desired size depending on the application.

[0192] Each component will be described below, however, these are merely examples and various modifications may be included as long as the effects of the present invention can be achieved.

[0193] (First and second glass layers) The first and second glass layers are not particularly limited in shape as long as they are capable of transmitting high frequency waves and then allowing the high frequency waves to reach the high frequency antenna circuit board via the adhesive layer. Examples of the shape include planar, curved, or other planar glass.

[0194] The material of the first and second glass layers is not particularly limited as long as it is a material generally used for window glass, and may be various light-transmitting transparent or semi-transparent organic glass members (e.g., acrylic members, polycarbonate members, etc.), but from the viewpoint of weather resistance and transparency, inorganic glass members such as soda-lime glass, borate glass, borosilicate glass, aluminosilicate glass, and quartz glass are preferably used. According to classification based on alkali components, non-alkali glass and low-alkali glass are included. The content of alkali metal components (e.g., Na2O, KO, Li2O) in the above glass members is preferably 15% by weight or less, more preferably 10% by weight or less.

[0195] The method of forming these glass layers may be any suitable method according to the shape and material of the glass. Typically, the glass member is prepared by melting a mixture containing a main raw material such as silica or alumina, an antifoaming agent such as mirabilite or antimony oxide, and a reducing agent such as carbon at a temperature of 1400°C to 1600°C, forming it into a thin plate, and then cooling it. Examples of the method of forming the thin plate of the glass member include a slot downdraw method, a fusion method, and a float method. The glass formed into a predetermined shape such as a plate by these methods may be thinned or may be given an uneven shape on the surface by anti-glare treatment, if necessary. In addition, in order to increase the smoothness, it may be chemically polished with a solvent such as hydrofluoric acid.

[0196] The first and second glass layers may be, for example, vehicle glazings (eg, vehicle glazings for cars, trains, airplanes, ships, etc.) or architectural glazings.

[0197] Alternatively, a second glass layer may be combined with the first glass layer and a high-frequency antenna circuit board may be disposed therebetween. The second glass layer is generally a glass member disposed opposite the first glass layer in the thickness direction, and may be made of the same material as or a different material from the first glass layer.

[0198] The dielectric constant εg of the first glass layer may be higher than the dielectric constant εf of the adhesive layer composed of at least one selected from the group consisting of polyvinyl acetal resins and ionomer resins, and may be, for example, 3.0 to 7.5, preferably 4.0 to 7.5, and more preferably 4.5 to 7.5 at a frequency of 28 GHz. Furthermore, when the first glass layer is composed of inorganic glass, the dielectric constant εg of the first glass layer is generally higher than the dielectric constant εf of the adhesive layer composed of at least one selected from the group consisting of polyvinyl acetal resins and ionomer resins, and may be, for example, 5.5 to 7.5, preferably 5.8 to 7.3, and more preferably 6.0 to 7.0.

[0199] The first glass layer may include a colored region, and an antenna circuit of a high-frequency antenna circuit board may be disposed in the colored region, as long as the first glass layer is capable of receiving high-frequency waves. The first glass layer may have a colored region partially, particularly in cases where visibility is required, such as in window glass or automobile windshields.

[0200] (adhesive layer) The adhesive layer is made of at least one resin selected from the group consisting of polyvinyl acetal resin and ionomer resin, has a dielectric constant lower than that of the first glass layer, and serves to allow the high frequency waves incident from the first glass layer to reach the high frequency antenna circuit board. The adhesive layer has a dielectric constant lower than that of the first glass layer when compared at the same frequency. Preferably, the dielectric constant εf of the adhesive layer relative to the dielectric constant εg of the first glass layer is within the range of the following formula (I).

[0201]

number

[0202] As a specific value, for example, at a frequency of 28 GHz, the dielectric constant εf of the adhesive layer may be, for example, εg-5 to εg-0.1, preferably εg-4.5 to εg-0.5, and more preferably εg-4 to εg-1.5, relative to the dielectric constant εg of the first glass layer.

[0203] In one embodiment, for example, at a frequency of 28 GHz, the dielectric constant εg of the first glass layer may be 5.5 to 7.5, preferably 5.8 to 7.3, and more preferably 6.0 to 7.0, and the dielectric constant εf of the adhesive layer may be, for example, 2.0 to 4.0, preferably 2.2 to 3.5, and more preferably 2.4 to 3.0.

[0204] In one embodiment, for example, at a frequency of 28 GHz, the dielectric tangent tanδg of the first glass layer may be 0.05 or less, preferably 0.03 or less, and more preferably 0.02 or less, and the dielectric tangent tanδf of the adhesive layer may be, for example, 0.05 or less, and preferably 0.03 or less.

[0205] In one embodiment, the thickness (df: unit: mm) of the adhesive layer on the high frequency antenna circuit board may be in the range of λ / 4×n-0.050 to λ / 4×n+0.050, preferably in the range of λ / 4×n-0.030 to λ / 4×n+0.030, more preferably in the range of λ / 4×n-0.025 to λ / 4×n+0.025, and particularly preferably in the range of λ / 4×n-0.010 to λ / 4×n+0.010, relative to the wavelength λ of the high frequency (range: 1 to 100 mm), where n is an integer (e.g., an integer of 1 to 10).

[0206] In one embodiment, the thickness (df: unit: mm) of the adhesive layer on the radio frequency antenna circuit board can be appropriately changed depending on the wavelength (λ) of the radio frequency and the dielectric constant εf of the adhesive layer, and is preferably in a range satisfying any one of the following formulae (II) to (II''), where n is an integer (for example, an integer from 1 to 10).

[0207]

number

[0208] More preferably, the range may satisfy the following formula (II').

number

[0209] More preferably, the range may satisfy the following formula (II'').

number

[0210] In one embodiment, the thickness (df: unit: mm) of the adhesive layer on the radio frequency antenna circuit board can be appropriately changed depending on the wavelength (λ) of the radio frequency and the dielectric constant of the adhesive layer, and is preferably in a range that satisfies any one of the following formulae (III) to (III''), where n is an integer (for example, an integer from 1 to 10).

[0211]

number

[0212] More preferably, the range may satisfy the following formula (III').

number

[0213] More preferably, the range may satisfy the following formula (III'').

number

[0214] In one embodiment, the thickness df (df') of the adhesive layer on the high-frequency antenna circuit board can be selected from a wide range of about 1 μm to 20.0 mm, and from the viewpoint of suppressing reflectance, it may be, for example, about 0.1 to 20.0 mm, preferably about 0.1 to 10.0 mm, and more preferably about 0.15 to 2.0 mm.

[0215] In another embodiment, the thickness df1 (df1') of the adhesive layer (1) on the high frequency antenna circuit board is preferably 370 μm or less, more preferably 300 μm or less, even more preferably 200 μm or less, even more preferably 100 μm or less, particularly preferably 60 μm or less, especially more preferably less than 50 μm, especially more preferably 45 μm or less, and most preferably 40 μm or less, from the viewpoint of suppressing the reflectance and reducing the thickness of the antenna system. The thickness df1 (df1') of the adhesive layer (1) on the high frequency antenna circuit board is preferably 1 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, and even more preferably 20 μm or more.

[0216] In yet another embodiment, the thickness df2 (df2') of the adhesive layer (2) on the high frequency antenna circuit board is preferably more than 370 μm, more preferably 500 μm or more, and even more preferably 750 μm or more, from the viewpoint of suppressing reflectance. Also, the thickness df2 (df2') of the adhesive layer (2) on the high frequency antenna circuit board is preferably 2.5 mm or less, more preferably 2.28 mm or less, even more preferably 1.6 mm or less, and even more preferably 0.85 mm or less.

[0217] In one embodiment, the total thickness da (da') of the adhesive layer can be selected from a wide range of about 1 μm to 20.0 mm, and may be, for example, about 0.1 to 20.0 mm, preferably about 0.1 to 10.0 mm, and more preferably about 0.15 to 2.0 mm.

[0218] In another embodiment, the total thickness da1 (da1') of the adhesive layer (1) is preferably 370 μm or less, more preferably 300 μm or less, even more preferably 200 μm or less, even more preferably 100 μm or less, particularly preferably 60 μm or less, particularly more preferably less than 50 μm, particularly more preferably 45 μm or less, and most preferably 40 μm or less, as a viewpoint of suppressing reflectance and thinning the thickness of the antenna system. In addition, the total thickness da1 (da1') of the adhesive layer (1) is preferably 1 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, and even more preferably 20 μm or more. Even if the adhesive layer is thin in this way, since it is made of a specific resin, it can be made to appropriately follow the unevenness of the circuit of the high frequency antenna circuit board, and thus the generation of air bubbles (remaining air) can be suppressed.

[0219] In yet another embodiment, the total thickness da2 (da2') of the adhesive layer (2) is preferably more than 370 μm, more preferably 500 μm or more, and even more preferably 750 μm or more, from the viewpoint of embedding a high-frequency antenna circuit board. The total thickness da2 (da2') of the adhesive layer (2) is preferably 2.5 mm or less, more preferably 2.28 mm or less, even more preferably 1.6 mm or less, and even more preferably 0.85 mm or less.

[0220] When a first adhesive layer and a second adhesive layer are adjacent to both sides of the high frequency antenna circuit board, respectively, both the first adhesive layer and the second adhesive layer may be adhesive layer (1) or adhesive layer (2). In addition, the first adhesive layer may be adhesive layer (1) and the second adhesive layer may be adhesive layer (2), and when a laminated glass having a high frequency antenna circuit board disposed therein is formed by thinning one of the adhesive layers, it is possible to produce the laminated glass without hollowing out the interlayer film for laminated glass to fill the step or without using a spacer to fill the step.

[0221] When a first adhesive layer and a second adhesive layer are adjacent to each other on both sides of a high-frequency antenna circuit board, the thickness and planar size of each adhesive layer may be the same or different from each other, depending on the embodiment and application of the antenna system.

[0222] The high-frequency antenna circuit board and the protective layer may be the same as those usable in the laminate.

[0223] <Antenna system manufacturing method> A manufacturing method of an antenna system in one embodiment of the present invention may include a step of overlaying a radio frequency antenna circuit board on at least one glass substrate via an adhesive layer and / or adhesive film composed of at least one resin selected from the group consisting of polyvinyl acetal resins and ionomer resins, and a step of heating the adhesive layer and / or adhesive film to a temperature equal to or higher than its softening temperature to pressure-bond the glass substrate and the radio frequency antenna circuit board.

[0224] In the present invention, at least one adhesive material selected from the group consisting of polyvinyl acetal resins and ionomer resins is used for bonding a glass substrate and a high-frequency antenna circuit board, and the two can be bonded by hot pressing. Furthermore, it is possible to prevent circuit breakage and deformation during the bonding, and even if the glass substrate is a curved glass such as an automobile windshield, it is possible to follow and prevent foaming and peeling. Furthermore, when forming an antenna system as a laminated glass in which a high-frequency antenna circuit board is embedded between glass substrates, lamination can be performed under general manufacturing conditions for laminated glass, so that extra steps can be omitted.

[0225] In the disposing step, the high frequency antenna circuit board in the laminate may be disposed by overlapping the adhesive layer of the laminate adjacent to the glass substrate. Alternatively, the high frequency antenna circuit board may be disposed via the adhesive film by overlapping an adhesive film composed of at least one selected from the group consisting of polyvinyl acetal resin and ionomer resin, and the high frequency antenna circuit board in this order on the glass substrate.

[0226] In the disposing step, components of the antenna system other than the laminate, the adhesive film, and the high-frequency antenna circuit board may be disposed. For example, a material for forming the above-mentioned protective layer, an adhesive material other than the polyvinyl acetal resin and the ionomer resin, etc. may be disposed.

[0227] In addition, it is possible to form an antenna system by using a first glass substrate and a second glass substrate as the glass substrate and embedding a high-frequency antenna circuit board in the laminated glass. In this case, in the arrangement step, for example, (i) a laminate having adhesive layers on both sides of a high frequency antenna circuit board may be used to stack the first glass substrate / adhesive layer of the laminate / high frequency antenna circuit board of the laminate / adhesive layer of the laminate / second glass substrate in this order; (ii) a laminate having an adhesive layer on one side of a high frequency antenna circuit board may be used to stack the first glass substrate / adhesive layer of the laminate / high frequency antenna circuit board of the laminate / adhesive film / second glass substrate in this order; (iii) a high frequency antenna circuit board alone may be used to stack the first glass substrate / adhesive film / high frequency antenna circuit board / adhesive film / second glass substrate in this order; (iv) a laminate having an adhesive layer on one side of a high frequency antenna circuit board may be used to stack the first glass substrate / adhesive layer of the laminate / high frequency antenna circuit board of the laminate / second glass substrate in this order; or (v) a high frequency antenna circuit board alone may be used to stack the first glass substrate / adhesive layer / high frequency antenna circuit board / second glass substrate in this order. In the above cases (iv) and (v), even if an adhesive layer or adhesive film is provided on only one side of the high-frequency antenna circuit board with respect to the first glass substrate and the second glass substrate, it is possible to form a laminated glass having an embedded high-frequency antenna circuit board as an antenna system in the heat-pressure bonding step described below.

[0228] The adhesive film is composed of at least one type selected from the group consisting of polyvinyl acetal resins and ionomer resins, and is not limited to a specific thickness as long as it is capable of forming an adhesive layer that constitutes the antenna system. For example, the thickness of the adhesive film can be selected within the range of 1 μm to 20.0 mm. From the viewpoint of embedding a high-frequency antenna circuit board, the thickness may be preferably more than 370 μm and not more than 2.5 mm, more preferably about 380 μm to 2.28 mm, even more preferably about 500 μm to 1.6 mm, and even more preferably 750 to 850 μm.

[0229] From the viewpoint of reducing the thickness of the antenna system, the thickness of the adhesive film is preferably 370 μm or less, more preferably 1 to 300 μm, even more preferably 5 to 200 μm, even more preferably 10 to 100 μm, particularly preferably 20 to 60 μm, particularly preferably 20 μm or more and less than 50 μm, particularly preferably 20 to 45 μm, and most preferably 20 to 40 μm. When the adhesive film is thin like this, since it is made of a specific resin, it can be made to appropriately follow the unevenness of the circuit of the high frequency antenna circuit board, and thus the generation of air bubbles (remaining air) can be suppressed.

[0230] The adhesive film may be composed of a polyvinyl acetal resin or an ionomer resin having the various components and properties used in the adhesive layer described above.

[0231] In the positioning step, the radio frequency antenna circuit board may be positioned by preliminarily heating the adhesive layer and / or adhesive film to fuse them, and after positioning, the glass substrate and the radio frequency antenna circuit board may be bonded by a heat-pressure bonding step described later.

[0232] In the thermocompression step, the adhesive layer and / or adhesive film are heated to a temperature equal to or higher than the softening temperature thereof to pressure-bond the glass substrate and the high-frequency antenna circuit board. For example, in the thermocompression step, the laminate obtained by superposing in the above-mentioned arrangement step may be heated to a temperature equal to or higher than the softening temperature of the adhesive layer and / or adhesive film to be pressure-bonded. The softening temperature may be the glass transition temperature of the adhesive layer and / or adhesive film. From the viewpoint of improving adhesion and suppressing flow, the heating temperature may be, for example, 70 to 200°C, preferably 90 to 180°C, more preferably 100 to 170°C, and even more preferably 110 to 150°C.

[0233] The thermocompression bonding step is preferably carried out under degassing and / or reduced pressure in order to prevent air from being mixed in. Degassing may be carried out by physically pushing air out of the bonding interface, and degassing or reducing pressure can be carried out by a known method described later.

[0234] In the thermocompression step, heating and pressurization can be performed by a conventionally known method, such as a method using a vacuum laminator, a method using a vacuum bag, a method using a vacuum ring, a method using a nip roll, etc. In addition, a method of putting the laminate into an autoclave step after the temporary pressure bonding can also be additionally performed.

[0235] For example, when a vacuum laminator is used, a known device can be used to perform heat-pressure bonding by laminating at a temperature of 100 to 200° C. (preferably 130 to 170° C.) under reduced pressure of 1 to 30,000 Pa. Also, when a vacuum bag or vacuum ring is used, heat-pressure bonding can be performed by laminating at a temperature of 130 to 170° C. under a pressure of about 20,000 Pa.

[0236] When using nip rolls, for example, a method may be used in which the adhesive layer and / or adhesive film are first provisionally pressed at a temperature lower than the softening temperature thereof, and then provisionally pressed at a temperature close to the softening temperature thereof. Specifically, the adhesive layer and / or adhesive film may be heated to 30 to 100°C with an infrared heater or the like, degassed with rolls, further heated to 50 to 150°C, and then pressed with rolls.

[0237] The autoclave process which is additionally performed after the temporary bonding depends on the thickness and configuration of the antenna system, but it is possible to perform heat bonding, for example, by carrying out the autoclave process under a pressure of about 1 to 1.5 MPa and at a temperature of 130 to 155°C for about 0.5 to 2 hours.

[0238] The antenna system of the present invention may include a protective layer on the surface opposite to the high frequency antenna circuit board bonded to the glass substrate. The protective layer may be a laminate having a protective layer, or a sheet for forming a protective layer may be disposed in the disposing step, or the protective layer may be formed after the heat-pressure bonding step. For example, in the arrangement step, a laminate having a protective layer and an adhesive layer may be used and the arrangement may be in the order of glass substrate / adhesive layer of laminate / high frequency antenna circuit board of laminate / protective layer of laminate; a laminate having an adhesive layer may be used and the arrangement may be in the order of glass substrate / adhesive layer of laminate / high frequency antenna circuit board of laminate / protective layer-forming sheet; or a high frequency antenna circuit board alone may be used and the arrangement may be in the order of glass substrate / adhesive film / high frequency antenna circuit board / protective layer-forming sheet. In addition, as a method for forming a protective layer after the thermocompression step, a method further including a step of placing a high-frequency antenna circuit board on a glass substrate via an adhesive layer or adhesive film, bonding the substrate by thermocompression, and then forming a protective layer on the non-adhesive surface of the high-frequency antenna circuit board can be mentioned.

[0239] In another embodiment of the present invention, a method for manufacturing an antenna system may include a step of interposing a compound absorbable by an adhesive layer and / or adhesive film composed of at least one type selected from the group consisting of polyvinyl acetal resins and ionomer resins between the adhesive layer and / or adhesive film and a glass substrate, and causing the adhesive layer and / or adhesive film to absorb the compound, thereby bonding a high-frequency antenna circuit board to a glass substrate.

[0240] In the present invention, in the adhesion between at least one adhesive layer and / or adhesive film selected from the group consisting of polyvinyl acetal resins and ionomer resins and a glass substrate, a compound absorbable by the adhesive layer and / or adhesive film is interposed, and the compound is absorbed by the adhesive layer and / or adhesive film, thereby making it possible to adhere the high frequency antenna circuit board to the glass substrate. By using such a method, the high frequency antenna circuit board can be easily attached and adhered to the glass substrate at a relatively low temperature. For example, the high frequency antenna circuit board can be attached to an existing window glass, a windshield of a car, etc. without locally heating to a high temperature, so that the glass substrate can be prevented from cracking.

[0241] The compound absorbable by the adhesive layer used in the adhesion step may be a plasticizer for the adhesive layer. For example, the above-mentioned plasticizer for the polyvinyl acetal resin may be used. By applying a plasticizer for the adhesive layer to the adhesive layer in the laminate, the laminate can be adhered to the glass substrate without softening the adhesive layer. As the compound absorbable by the adhesive layer, triethylene glycol-bis-(2-ethylbutanoate), triethylene glycol-bis-(2-ethylhexanoate), dihexyl adipate, dibutyl sebacate, di(butoxyethyl) adipate, and di(butoxyethoxyethyl) adipate are preferred, triethylene glycol-bis-(2-ethylhexanoate), di(butoxyethyl) adipate, and di(butoxyethoxyethyl) adipate are more preferred, and di(butoxyethyl) adipate and di(butoxyethoxyethyl) adipate are particularly preferred.

[0242] In the bonding step, the adhesive layer may be heated to a degree that does not soften it, and from the viewpoint of bonding at a low temperature, the heating temperature may be 120° C. or lower, preferably 100° C. or lower, more preferably 80° C. or lower, even more preferably 50° C. or lower, and even more preferably 40° C. or lower. The lower limit of the heating temperature may be, for example, 25° C. or higher. EXAMPLES

[0243] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0244] [Dielectric constant and dissipation factor] The dielectric constant and dielectric loss tangent of the films used in the adhesive layer and high frequency insulating layer described below were measured in accordance with JIS R 1660-2 at a frequency of 28 GHz (25°C) using a Fabry-Perot resonator (Model No. DPS03) manufactured by Keycom Co., Ltd. The measurements were performed in one direction on a plane and in both directions perpendicular to the same (XY directions).

[0245] [High frequency antenna circuit board, thickness of adhesive layer] The thickness of the high frequency antenna circuit board was measured using a micrometer (Model 227-201-CLM-15QM, manufactured by Mitutoyo Corporation). The total thickness of the adhesive layer was measured using a film used as the adhesive layer. The thickness of the adhesive layer may be obtained by measuring the thickness of the entire antenna system, and the thickness of the high frequency antenna circuit board and glass in the antenna system, and subtracting the thickness of the high frequency antenna circuit board and glass from the thickness of the entire antenna system.

[0246] [Polyvinyl acetal resin solution viscosity] The polyvinyl acetal resin constituting the polyvinyl acetal resin film was dissolved in a mixed solvent of toluene / ethanol = 1 / 1 (mass ratio) to a concentration of 10 mass % to prepare a solution. The viscosity of this solution was measured using a Brookfield type (B type) viscometer at 20 ° C. and a rotation speed of 30 rpm.

[0247] [Example 1] <Production of high frequency antenna circuit board> Copper foil (Fukuda Metal Foil and Powder Co., Ltd., electrolytic copper foil "H9A", thickness 12 μm) was superimposed on both sides of a thermoplastic liquid crystal polymer film (Kuraray Co., Ltd., Vecstar (registered trademark), thickness 50 μm, dielectric constant in X direction: 3.4, dielectric constant in Y direction: 3.4, dielectric loss tangent in X direction: 0.002, dielectric loss tangent in Y direction: 0.002) and a vacuum hot press was used to set the heating plate to 290 ° C. and press the film under a pressure of 4 MPa for 15 minutes to produce a copper-clad laminate having a copper foil / thermoplastic liquid crystal polymer film / copper foil configuration. A part of the copper foil on one side of the obtained copper-clad laminate was removed with an etching solution to form a circuit, and this operation was repeated to produce a high-frequency antenna circuit board (length 5 cm, width 5 cm) having a thickness of 400 μm.

[0248] <Preparation of polyvinyl acetal resin film> Polyvinyl butyral resin 1 (hydroxyl group amount 19.8 mass%, acetalization degree 70.8 mol%, acetyl group amount 1.0 mass%, resin viscosity 152 mPa s) and polyvinyl butyral resin 2 (hydroxyl group amount 20.1 mass%, acetalization degree 70.4 mol%, acetyl group amount 0.9 mass%, resin viscosity 1410 mPa s) were blended in a mass ratio of 75:25, melt-kneaded, extruded into strands, and pelletized. The resulting pellets were melt-extruded using a single-screw extruder and a T-die, and a polyvinyl acetal resin film with a smooth surface and a thickness of 50 μm (dielectric constant in X direction: 2.5, dielectric constant in Y direction: 2.5, dielectric loss tangent in X direction: 0.01, dielectric loss tangent in Y direction: 0.01, plasticizer content: 0 mass%, resin viscosity: 245 mPa s) was obtained.

[0249] <Preparation of Laminate> On a lower glass of 20 cm in length, 10 cm in width, and 3 mm in thickness, a Teflon (registered trademark) sheet with one side embossing, the dried polyvinyl acetal resin film prepared above, 5 cm in length, 5 cm in width, and 50 μm in thickness, the high-frequency antenna circuit board prepared above (5 cm in length, 5 cm in width), a Teflon (registered trademark) sheet with one side embossing, and an upper glass of 5 cm in length, 5 cm in width, and 3 mm in thickness were stacked and fixed in this order. Note that the polyvinyl acetal resin film, the high-frequency antenna circuit board, and the upper glass were aligned so as to overlap each other. The Teflon (registered trademark) sheet adjacent to the polyvinyl acetal resin film was placed so that the embossed surface was in contact with the polyvinyl acetal resin film. The Teflon (registered trademark) sheet adjacent to the high frequency antenna circuit board was placed so that the mirror surface was in contact with the high frequency antenna circuit board. The high frequency antenna circuit board was placed so that the surface having the circuit was in contact with the polyvinyl acetal resin film. These were heated in a vacuum laminator at 140°C for 15 minutes under vacuum, and then the upper chamber was set to -10 kPa (differential pressure with the lower chamber: approximately 90 kPa) and held for 15 minutes. The pressure was then returned to normal pressure, and the Teflon (registered trademark) sheets and upper and lower glass sheets arranged above and below were removed to produce a laminate in the following order: polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high-frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer).

[0250] <Fabrication of antenna system> The laminate (5 cm long, 5 cm wide) was placed on a lower glass with a length of 20 cm, a width of 10 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, so that the polyvinyl acetal resin film (adhesive layer) was in contact with the lower glass, and a Teflon (registered trademark) sheet and an upper glass with a length of 5 cm, a width of 5 cm, and a thickness of 3 mm were placed on top of the laminate and fixed in this order. The high-frequency antenna circuit board was disposed in an area 2 cm to 7 cm inward from the vertical end of the lower glass. The laminate and the upper glass were aligned so that they overlapped each other. These were heated at 140°C for 15 minutes under vacuum in a vacuum laminator, and then the upper chamber was set to -10kPa (pressure difference with the lower chamber of about 90kPa) and held for 15 minutes, and then the pressure was returned to normal pressure, and the Teflon (registered trademark) sheet and the upper glass were removed, and the glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) were laminated in this order, and an antenna system was obtained in which a high frequency antenna circuit board was disposed on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no breakage or deformation of the circuit was observed. In addition, in the obtained antenna system, since the adhesive layer has a dielectric constant smaller than that of the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0251] [Example 2] <Fabrication of antenna system> The laminate (5 cm long, 5 cm wide) obtained in Example 1 was placed on the lower glass having a length of 20 cm, a width of 10 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, so that the polyvinyl acetal resin film (adhesive layer) was in contact with the lower glass, and the dried polyvinyl acetal resin film produced in Example 1 having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm and a thin glass having a length of 5 cm, a width of 5 cm, and a thickness of 1 mm were placed on top of it and fixed in this order. The high frequency antenna circuit board was disposed in an area 2 cm to 7 cm inward from the vertical end of the lower glass. The laminate and the thin glass were aligned so that they overlap each other. These were heated at 140°C for 15 minutes under vacuum in a vacuum laminator, and then the upper chamber was set to -10kPa (pressure difference with the lower chamber of about 90kPa) and held for 15 minutes, and then the pressure was returned to normal pressure, and the glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (adhesive layer) / thin glass (protective layer) were laminated in this order, and an antenna system was obtained in which a high frequency antenna circuit board with a protective glass plate was arranged on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no breakage or deformation of the circuit was observed. In addition, in the obtained antenna system, since the adhesive layer has a dielectric constant smaller than that of the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0252] [Example 3] <Preparation of Laminate> On a glass measuring 20 cm in length, 10 cm in width and 3 mm in thickness, a Teflon (registered trademark) sheet with one side embossing, a dried polyvinyl acetal resin film measuring 5 cm in length, 5 cm in width and 50 μm in thickness prepared in Example 1, a high-frequency antenna circuit board (5 cm in length, 5 cm in width) prepared in Example 1, a dried polyvinyl acetal resin film measuring 5 cm in length, 5 cm in width and 50 μm in thickness prepared in Example 1, and a thin glass sheet measuring 5 cm in length, 5 cm in width and 1 mm in thickness were stacked and fixed in this order. The polyvinyl acetal resin film, the high-frequency antenna circuit board and the thin glass sheet were aligned so as to overlap each other. The Teflon sheet was placed so that the embossed surface was in contact with the polyvinyl acetal resin film, and the high-frequency antenna circuit board was placed so that the surface having the circuit was in contact with the polyvinyl acetal resin film adjacent to the Teflon sheet. These were heated in a vacuum laminator at 140°C for 15 minutes under vacuum, and then the upper chamber was set to -10 kPa (differential pressure with the lower chamber: approximately 90 kPa) and held for 15 minutes. The pressure was then returned to normal pressure, and the Teflon (registered trademark) sheet and glass were removed to produce a laminate in the following order: polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high-frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (adhesive layer) / thin glass (protective layer).

[0253] <Fabrication of antenna system> The laminate (5 cm long, 5 cm wide) was fixed on a piece of glass measuring 20 cm long, 10 cm wide, 3 mm thick, with a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, so that the polyvinyl acetal resin film (adhesive layer) was in contact with the glass. The laminate was placed on the glass in an area 2 cm to 7 cm inward from the end of the glass in the vertical direction. These were heated at 140°C for 15 minutes under vacuum in a vacuum laminator, and then the upper chamber was set to -10kPa (pressure difference with the lower chamber of about 90kPa) and held for 15 minutes, and then the pressure was returned to normal pressure, and the glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (adhesive layer) / thin glass (protective layer) were laminated in this order, and an antenna system was obtained in which a high frequency antenna circuit board with a protective glass plate was arranged on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no breakage or deformation of the circuit was observed. In addition, in the obtained antenna system, since the adhesive layer has a dielectric constant smaller than that of the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0254] [Example 4] <Preparation of Laminate> On the lower glass having a length of 20 cm, a width of 10 cm, and a thickness of 3 mm, a Teflon (registered trademark) sheet with one side embossing, a dried polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm prepared in Example 1, a high-frequency antenna circuit board (length of 5 cm, width of 5 cm) prepared in Example 1, a dried polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm prepared in Example 1, a Teflon (registered trademark) sheet with one side embossing, and an upper glass having a length of 5 cm, a width of 5 cm, and a thickness of 3 mm were stacked and fixed in this order. The Teflon (registered trademark) sheet was arranged so that the embossed surface was in contact with the polyvinyl acetal resin film. The high-frequency antenna circuit board was arranged so that the surface having the circuit was in contact with the polyvinyl acetal resin film on the lower glass side. These were heated in a vacuum laminator at 140°C for 15 minutes under vacuum, and then the upper chamber was set to -10 kPa (differential pressure with the lower chamber: approximately 90 kPa) and held for 15 minutes. The pressure was then returned to normal pressure, and the Teflon (registered trademark) sheets and upper and lower glass sheets arranged above and below were removed to produce a laminate in the following order: polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high-frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (adhesive layer).

[0255] <Fabrication of antenna system> The laminate (5 cm long, 5 cm wide) was placed on a glass with a length of 20 cm, a width of 10 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, so that the polyvinyl acetal resin film (adhesive layer) adjacent to the circuit layer was in contact with the glass, and a thin glass sheet with a length of 5 cm, a width of 5 cm, and a thickness of 1 mm was placed on top of it and fixed. The high-frequency antenna circuit board was disposed in an area 2 cm to 7 cm inward from the longitudinal end of the glass. The laminate and the thin glass sheet were aligned so that they overlapped each other. These were heated at 140°C for 15 minutes under vacuum in a vacuum laminator, and then the upper chamber was set to -10kPa (pressure difference with the lower chamber of about 90kPa) and held for 15 minutes, and then the pressure was returned to normal pressure, and the glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (adhesive layer) / thin glass (protective layer) were laminated in this order, and an antenna system was obtained in which a high frequency antenna circuit board with a protective glass plate was arranged on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no breakage or deformation of the circuit was observed. In addition, in the obtained antenna system, since the adhesive layer has a dielectric constant smaller than that of the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0256] [Example 5] <Preparation of Laminate> Instead of the polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm, a plasticized polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 0.38 mm (dielectric constant in the X direction: 2.7, dielectric constant in the Y direction: 2.7, dielectric loss tangent in the X direction: 0.02, dielectric loss tangent in the Y direction: 0.02) containing 72 mass% of polyvinyl butyral resin (hydroxyl group amount 28.8 mass%, viscosity average polymerization degree 1700) and 28 mass% of triethylene glycol-bis-(2-ethylhexanoate) was used. A laminate was produced in the same manner as in Example 1, in which the plasticized polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) were laminated in this order.

[0257] <Fabrication of antenna system> Except for using the above laminate instead of the laminate of Example 1, the laminate was laminated in the order of glass (first glass layer) / plasticized polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) to obtain an antenna system in which a high frequency antenna circuit board is disposed on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no breakage or deformation of the circuit was observed. In addition, in the obtained antenna system, since the adhesive layer has a smaller dielectric constant than the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0258] [Example 6] <Fabrication of antenna system> The laminate of Example 5 was used instead of the laminate of Example 1, and the plasticized polyvinyl acetal resin film of 5 cm in length, 5 cm in width, and 0.38 mm in thickness used in Example 5 was used instead of the polyvinyl acetal resin film of 5 cm in length, 5 cm in width, and 50 μm in thickness used in Example 5. Except for this, the laminate was laminated in the order of glass (first glass layer) / plasticized polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as insulating layer) / copper foil (conductor layer) / plasticized polyvinyl acetal resin film (adhesive layer) / thin glass (protective layer) to obtain an antenna system in which a high frequency antenna circuit board with a protective glass plate was disposed on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no disconnection or deformation of the circuit was observed. Furthermore, in the obtained antenna system, since the adhesive layer has a smaller dielectric constant than the glass, high frequency waves incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0259] [Example 7] <Preparation of Laminate> A laminate was produced in the same manner as in Example 1, except that a 5 cm long, 5 cm wide, 50 μm thick ionomer resin film (Kuraray Co., Ltd., SentryGlas (registered trademark) SG5000 thinned by heat pressing, X-direction dielectric constant: 2.2, Y-direction dielectric constant: 2.2, X-direction dielectric loss tangent: 0.002, Y-direction dielectric loss tangent: 0.002) was used instead of the 5 cm long, 5 cm wide, 50 μm thick polyvinyl acetal resin film. The laminate was produced in the same manner as in Example 1, except that a 5 cm long, 5 cm wide, 50 μm thick ionomer resin film ... (Kuraray Co., Ltd., SentryGlas (registered trademark) SG5000 thinned by heat pressing, X-direction dielectric constant: 2.2, Y-direction dielectric loss tangent: 0.002, Y-direction dielectric loss tangent: 0.002) was used instead of the 5 cm long, 5 cm wide, 50 μm thick polyvinyl acetal resin film.

[0260] <Fabrication of antenna system> The laminate of Example 1 was replaced with the above laminate, and the polyvinyl acetal resin film of 5 cm in length, 5 cm in width, and 50 μm in thickness was replaced with an ionomer resin film of 5 cm in length, 5 cm in width, and 50 μm in thickness (a film made by thinning SentryGlas (registered trademark) SG5000 by heat pressing, manufactured by Kuraray Co., Ltd.) was replaced with an ionomer resin film of 5 cm in length, 5 cm in width, and 50 μm in thickness. The laminate was laminated in the order of glass (first glass layer), ionomer resin film (adhesive layer), circuit (circuit layer), high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer), copper foil (conductor layer), ionomer resin film (adhesive layer), and thin glass (protective layer), and an antenna system was obtained in which a high frequency antenna circuit board with a protective glass plate was disposed on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no disconnection or deformation of the circuit was observed. Furthermore, in the obtained antenna system, since the adhesive layer has a smaller dielectric constant than the glass, high frequency waves incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0261] [Example 8] <Preparation of Laminate> A laminate is prepared in the same manner as in Example 1, except that a polyvinyl acetal resin film measuring 5 cm in length, 5 cm in width and 30 μm in thickness is used instead of the polyvinyl acetal resin film measuring 5 cm in length, 5 cm in width and 50 μm in thickness, and a laminate is prepared in the following order: polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high-frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer).

[0262] <Fabrication of antenna system> Except for using the above laminate instead of the laminate of Example 1, the laminate is laminated in the same manner as in Example 2 in the order of glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (adhesive layer) / thin glass (protective layer), and an antenna system is obtained in which a high frequency antenna circuit board with a protective glass plate is disposed on a part of the glass. The polyvinyl acetal resin film having a thickness of 30 μm is composed of the same polyvinyl acetal resin as the polyvinyl acetal resin film produced in Example 1, and is therefore presumed to have the same dielectric constant. In the obtained antenna system, the adhesive layer has a dielectric constant smaller than that of the glass, and it is presumed that the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0263] [Example 9] <Fabrication of antenna system> On the lower glass having a length of 20 cm, a width of 10 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, the dried polyvinyl acetal resin film produced in Example 1 having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm, the high frequency antenna circuit board produced in Example 1 (length of 5 cm, width of 5 cm), a Teflon (registered trademark) sheet, and an upper glass having a length of 5 cm, a width of 5 cm, and a thickness of 3 mm were stacked and fixed in this order. The high frequency antenna circuit board was arranged so that the surface having the circuit was in contact with the polyvinyl acetal resin film. The polyvinyl acetal resin film, the high frequency antenna circuit board, and the upper glass were aligned so that they overlapped with each other. These were heated at 140°C for 15 minutes under vacuum in a vacuum laminator, and then the upper chamber was set to -10kPa (pressure difference with the lower chamber of about 90kPa) and held for 15 minutes, and then the pressure was returned to normal pressure, and the Teflon (registered trademark) sheet and the upper glass were removed, and the glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) were laminated in this order, and an antenna system was obtained in which a high frequency antenna circuit board was disposed on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no breakage or deformation of the circuit was observed. In addition, in the obtained antenna system, since the adhesive layer has a dielectric constant smaller than that of the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0264] [Example 10] <Fabrication of antenna system> On the lower glass having a length of 20 cm, a width of 10 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, a dried polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm prepared in Example 1, a high-frequency antenna circuit board (length of 5 cm, width of 5 cm) prepared in Example 1, a dried polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm prepared in Example 1, and a thin glass plate having a length of 5 cm, a width of 5 cm, and a thickness of 1 mm were stacked and fixed in this order. The high-frequency antenna circuit board was arranged so that the surface having the circuit was in contact with the polyvinyl acetal resin film on the lower glass side. The high-frequency antenna circuit board was arranged in an area 2 cm to 7 cm inward from the vertical end of the lower glass. The high-frequency antenna circuit board, the two polyvinyl acetal resin films, and the thin glass sheet were aligned so as to overlap each other. These were placed in a vacuum bag, and after decompressing at room temperature for 15 minutes, the temperature was raised to 135°C while still under reduced pressure and held for 30 minutes, and then the temperature was lowered and the reduced pressure was released to obtain an antenna system in which glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (adhesive layer) / thin glass (protective layer) were laminated in this order, and a high frequency antenna circuit board with a protective glass plate was disposed on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no breaks or deformations were observed in the circuit. In addition, in the obtained antenna system, since the adhesive layer has a smaller dielectric constant than the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0265] [Example 11] <Fabrication of antenna system> The same procedure as in Example 9 was used except that a plasticized polyvinyl acetal resin film of 5 cm in length, 5 cm in width, and 0.38 mm in thickness used in Example 5 was used instead of the polyvinyl acetal resin film of 5 cm in length, 5 cm in width, and 50 μm in thickness. The glass (first glass layer) / plasticized polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) were laminated in this order, and an antenna system in which a high frequency antenna circuit board was disposed on a part of the glass was obtained. No partial peeling or foaming was observed in the obtained antenna system, and no breaks or deformations in the circuit were observed. In addition, in the obtained antenna system, since the adhesive layer has a smaller dielectric constant than the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0266] [Example 12] <Fabrication of antenna system> On a glass having a length of 20 cm, a width of 10 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, a dried plasticized polyvinyl acetal resin film having a length of 7 cm, a width of 7 cm, and a thickness of 0.38 mm used in Example 5, a high-frequency antenna circuit board (length of 5 cm, width of 5 cm) prepared in Example 1 in the center of the plasticized polyvinyl acetal resin film, a dried polyvinyl acetal resin film having a length of 7 cm, a width of 7 cm, and a thickness of 50 μm prepared in Example 1, and a thin glass plate having a length of 7 cm, a width of 7 cm, and a thickness of 1 mm were stacked and fixed in this order. The high-frequency antenna circuit board was arranged so that the surface having the circuit was in contact with the plasticized polyvinyl acetal resin film. The high-frequency antenna circuit board was arranged in an area 2 cm to 7 cm inward from the longitudinal end of the glass. The two polyvinyl acetal resin films and the thin glass sheet were aligned so as to overlap each other. These were placed in a vacuum bag, decompressed at room temperature for 15 minutes, heated to 100°C while still decompressed, and held for 30 minutes, then cooled and released from the decompression, temporarily bonded, and then placed in an autoclave and treated at 140°C and 12MPa for 30 minutes to obtain an antenna system in which glass (first glass layer) / plasticized polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (adhesive layer) / thin glass (protective layer) were laminated in this order, and a high frequency antenna circuit board with a protective glass plate was disposed on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no breakage or deformation of the circuit was observed. In addition, in the obtained antenna system, since the adhesive layer has a smaller dielectric constant than the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0267] [Example 13] <Fabrication of antenna system> The laminate obtained in Example 1 was laminated on a lower glass having a length of 30 cm, a width of 30 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, so that the polyvinyl acetal resin film (adhesive layer) was in contact with the lower glass, and on top of that, a plasticized polyvinyl acetal resin intermediate film having a length of 30 cm, a width of 30 cm, and a thickness of 0.76 mm, containing 72% by mass of polyvinyl butyral resin (hydroxyl group amount 28.8% by mass, viscosity average polymerization degree 1700) and 28% by mass of triethylene glycol-bis-(2-ethylhexanoate), and an upper glass having a length of 30 cm, a width of 30 cm, and a thickness of 3 mm were laminated and fixed in this order. The high frequency antenna circuit board was disposed in the center of the surface direction of the lower glass. These were placed in a vacuum bag, decompressed at room temperature for 15 minutes, heated to 100°C while still under reduced pressure, and held for 30 minutes. The temperature was then lowered, the decompression was released, and the material was temporarily pressed. The material was then placed in an autoclave and treated at 140°C and 12MPa for 30 minutes to obtain an antenna system in which the layers were laminated in the order of glass (first glass layer), polyvinyl acetal resin film (first adhesive layer), circuit (circuit layer), high-frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer), copper foil (conductor layer), plasticized polyvinyl acetal resin intermediate film (second adhesive layer), and glass (second glass layer), with the high-frequency antenna circuit board sealed inside the laminated glass. In the antenna system obtained, no foaming or significant optical unevenness was observed around the antenna circuit. In addition, in the antenna system obtained, the adhesive layer has a smaller dielectric constant than the glass, so that the high-frequency waves incident on the glass can pass through the adhesive layer and reach the high-frequency antenna circuit board.

[0268] [Example 14] <Fabrication of antenna system> A dried polyvinyl acetal resin film of 7 cm in length, 7 cm in width, and 50 μm in thickness prepared in Example 1 was superimposed on a lower glass having a length of 30 cm, a width of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01. The high-frequency antenna circuit board (5 cm in length, 5 cm in width) prepared in Example 1 was superimposed and arranged in the center of the polyvinyl acetal resin film, and a plasticized polyvinyl acetal resin intermediate film of 30 cm in length, 30 cm in width, and 0.76 mm in thickness used in Example 13 and an upper glass having a length of 30 cm in length, 30 cm in width, and a thickness of 3 mm were superimposed and fixed in this order. The high-frequency antenna circuit board was arranged so that the surface having the circuit was in contact with the polyvinyl acetal resin film. The high-frequency antenna circuit board was disposed in the center of the surface direction of the lower glass. These were placed in a vacuum bag, decompressed at room temperature for 15 minutes, heated to 100°C while still under reduced pressure, and held for 30 minutes. The temperature was then lowered, the decompression was released, and the material was temporarily pressed. The material was then placed in an autoclave and treated at 140°C and 12MPa for 30 minutes to obtain an antenna system in which the layers were laminated in the order of glass (first glass layer), polyvinyl acetal resin film (first adhesive layer), circuit (circuit layer), high-frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer), copper foil (conductor layer), plasticized polyvinyl acetal resin intermediate film (second adhesive layer), and glass (second glass layer), with the high-frequency antenna circuit board sealed inside the laminated glass. In the antenna system obtained, no foaming or significant optical unevenness was observed around the antenna circuit. In addition, in the antenna system obtained, the adhesive layer has a smaller dielectric constant than the glass, so that the high-frequency waves incident on the glass can pass through the adhesive layer and reach the high-frequency antenna circuit board.

[0269] [Example 15] <Fabrication of antenna system> An ionomer resin film (manufactured by Kuraray Co., Ltd., SentryGlas (registered trademark) SG5000 thinned by heat pressing, X-direction dielectric constant: 2.2, Y-direction dielectric constant: 2.2, X-direction dielectric tangent: 0.002, Y-direction dielectric tangent: 0.002) measuring 7 cm in length, 7 cm in width, and 50 μm in thickness was placed on the lower glass having dimensions of 30 cm in length, 30 cm in width, 3 mm in thickness, dielectric constant in the X direction: 6.5, dielectric constant in the Y direction: 6.5, dielectric tangent in the X direction: 0.01, and dielectric tangent in the Y direction: 0.01) and the high-frequency antenna circuit board (5 cm in length, 5 cm in width) produced in Example 1 was placed on the center of the polyvinyl acetal resin film, and a dried ionomer resin intermediate film (manufactured by Kuraray Co., Ltd., SentryGlas (registered trademark) The lower glass was fixed in place with a thickness of 30 mm and a thickness of 30 cm. The high-frequency antenna circuit board was placed so that the surface with the circuit was in contact with the ionomer resin film. The high-frequency antenna circuit board was placed in the center of the surface of the lower glass. These were placed in a vacuum bag, decompressed at room temperature for 15 minutes, heated to 100°C while still under reduced pressure, and held for 30 minutes. After that, the temperature was lowered, the decompression was released, and the material was temporarily pressed. The material was then placed in an autoclave and treated at 135°C and 12MPa for 30 minutes to obtain an antenna system in which the layers were laminated in the order of glass (first glass layer), ionomer resin film (first adhesive layer), circuit (circuit layer), high-frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer), copper foil (conductor layer), ionomer resin intermediate film (second adhesive layer), and glass (second glass layer), and the high-frequency antenna circuit board was sealed inside the laminated glass. In the antenna system obtained, no foaming or large optical unevenness was observed around the antenna circuit. In addition, in the antenna system obtained, the adhesive layer has a smaller dielectric constant than the glass, so that the high-frequency waves incident on the glass can pass through the adhesive layer and reach the high-frequency antenna circuit board.

[0270] [Example 16] <Fabrication of antenna system> An appropriate amount of triethylene glycol-di-(2-ethylhexanoate) was applied to the polyvinyl acetal resin film surface of the laminate obtained in Example 1, and the laminate was attached to a glass sheet having dimensions of 20 cm length, 10 cm width, 3 mm thickness, X-direction dielectric constant: 6.5, Y-direction dielectric constant: 6.5, X-direction dielectric loss tangent: 0.01, and Y-direction dielectric loss tangent: 0.01, without allowing air to enter the glass sheet. The high-frequency antenna circuit board was disposed in an area 2 cm to 7 cm inward from the longitudinal end of the glass sheet. By heating these for 1 hour in a hot air dryer at 50°C, glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) were laminated in this order, and an antenna system was obtained in which a high frequency antenna circuit board was disposed on a part of the glass. Even when a shear force was applied to the obtained antenna system, no deviation of the film was observed. Furthermore, in the obtained antenna system, since the adhesive layer has a smaller dielectric constant than the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0271] [Example 17] <Fabrication of antenna system> An appropriate amount of triethylene glycol-di-(2-ethylhexanoate) was applied to the polyvinyl acetal resin film surface of the laminate obtained in Example 3, and the laminate was attached to a glass sheet having dimensions of 20 cm length, 10 cm width, 3 mm thickness, X-direction dielectric constant: 6.5, Y-direction dielectric constant: 6.5, X-direction dielectric loss tangent: 0.01, and Y-direction dielectric loss tangent: 0.01, without allowing air to enter the glass sheet. The high-frequency antenna circuit board was disposed in an area 2 cm to 7 cm inward from the longitudinal end of the glass sheet. By heating these for 1 hour in a hot air dryer at 50 ° C, glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (adhesive layer) / thin glass (protective layer) were laminated in this order, and an antenna system was obtained in which a high frequency antenna circuit board with a protective glass plate was arranged on a part of the glass. Even when a shear force was applied to the obtained antenna system, no deviation of the film was observed. Furthermore, in the obtained antenna system, since the adhesive layer has a smaller dielectric constant than the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0272] [Example 18] <Fabrication of antenna system> Except for using dibutoxyethyl adipate instead of triethylene glycol-di-(2-ethylhexanoate), the same procedure as in Example 17 was used, and glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (adhesive layer) / thin glass (protective layer) were laminated in this order, and an antenna system was obtained in which a high frequency antenna circuit board with a protective glass plate was disposed on a part of the glass. Even when a shear force was applied to the obtained antenna system, no deviation of the film was observed. In addition, in the obtained antenna system, since the adhesive layer has a smaller dielectric constant than the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0273] [Example 19] <Fabrication of antenna system> In the same manner as in Example 17, except that the heating in the hot air dryer was changed to 30°C and 24 hours, glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (adhesive layer) / thin glass (protective layer) were laminated in this order, and an antenna system was obtained in which a high frequency antenna circuit board with a protective glass plate was arranged on a part of the glass. Even when a shear force was applied to the obtained antenna system, no deviation of the film was observed. In addition, in the obtained antenna system, since the adhesive layer has a dielectric constant smaller than that of the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0274] [Example 20] <Fabrication of antenna system> Except for changing the heating temperature in the hot air dryer to 30°C, the same procedure as in Example 18 was followed, and the glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (adhesive layer) / thin glass (protective layer) were laminated in this order, and an antenna system was obtained in which a high frequency antenna circuit board with a protective glass plate was disposed on a part of the glass. No film shift was observed even when a shear force was applied to the obtained antenna system. In addition, in the obtained antenna system, since the adhesive layer has a smaller dielectric constant than the glass, the high frequency incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0275] [Example 21] <Fabrication of antenna system> A polyvinyl acetal resin film (V200KE, manufactured by Kuraray Co., Ltd., thickness 700 μm, dielectric constant in X direction: 2.7, dielectric constant in Y direction: 2.7, dielectric dissipation factor in X direction: 0.02, dielectric dissipation factor in Y direction: 0.02) measuring 3 cm in length and 3 cm in width was placed on a piece of glass measuring 20 cm in length, 10 cm in width, and 3.5 mm in thickness, with a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric dissipation factor in the X direction: 0.01, and a dielectric dissipation factor in the Y direction: 0.01, on which the upper end of the film was 2 cm below (inward) from the upper end of the glass in the vertical direction and the center of the film in the horizontal direction overlapped with the center of the glass in the horizontal direction. The high-frequency antenna circuit board produced in Example 1 was placed on top of the film so that the surface having the circuit was in contact with the polyvinyl acetal resin film. Then, the glass was placed in a vacuum bag while the position of the high frequency antenna circuit board was held, and treated at 100°C under reduced pressure for 30 minutes. After cooling, the reduced pressure was released, and the high frequency antenna circuit board was pre-laminated to the glass. Then, this was placed in an autoclave and treated at 140°C and 1.2MPa for 30 minutes, and the glass (first glass layer) / polyvinyl acetal resin film (adhesive layer) / circuit (circuit layer) / high frequency antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) were laminated in this order, and an antenna system in which a high frequency antenna circuit board was disposed on a part of the glass was obtained. In the obtained antenna system, the thickness df of the adhesive layer was 700μm, and the range of λ / 4×n±0.050mm (n=2) was satisfied for the high frequency of the target wavelength λ (1.47mm).

[0276] When a high frequency wave with a wavelength λ is incident on the obtained antenna system from the glass side, the polyvinyl acetal resin film has a dielectric constant smaller than that of the glass and within the range satisfying the above formula (I), and therefore the high frequency wave incident on the glass can pass through the polyvinyl acetal resin layer, which is the adhesive layer, and reach the high frequency antenna circuit board. Furthermore, since the thickness of the adhesive layer satisfies the range of λ / 4×n±0.050 mm, high frequency waves can be efficiently delivered to the high frequency antenna circuit board.

[0277] [Example 22] In place of the adhesive layer used in Example 21, a polyvinyl acetal resin film [MFR (190°C, 2.16 kg) 0.75 g / 10 min, thickness 50 μm, dielectric constant in X direction: 2.5, dielectric constant in Y direction: 2.5, dielectric loss tangent in X direction: 0.01, dielectric loss tangent in Y direction: 0.01] is used in multiple layers. When an antenna system is produced in the same manner as in Example 21, the adhesive layer has a smaller dielectric constant than the glass, as in Example 21, and therefore the high frequency wave incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board.

[0278] [Example 23] In the case where an antenna system is produced in the same manner as in Example 21, except that an ionomer resin film (manufactured by Kuraray Co., Ltd., SGR5000, thickness 1000 μm, dielectric constant in X direction: 2.2, dielectric constant in Y direction: 2.2, dielectric loss tangent in X direction: 0.002, dielectric loss tangent in Y direction: 0.002) is used instead of the adhesive layer used in Example 21, the adhesive layer has a dielectric constant smaller than that of glass, similar to Example 21, and therefore the high frequency wave incident on the glass can pass through the adhesive layer and reach the high frequency antenna circuit board. [Industrial Applicability]

[0279] The laminate of the present invention is useful for producing an antenna system that can handle high frequencies. The antenna system of the present invention suppresses attenuation of high frequencies, improves the transmission characteristics of the high frequency antenna circuit board for high frequencies, and can exchange a large amount of information. Therefore, it can be usefully used as an antenna system for vehicles such as so-called connected cars for automatic driving and continuous communication by on-board devices, windows and walls of buildings, and antenna systems for small cell base stations by installing the antenna system on various civil engineering structures (railroad facilities, road facilities, energy facilities, dams and river facilities, water supply and sewerage facilities, and airport facilities). For example, the antenna system of the present invention can be used by forming the window glass of a vehicle or building, or by attaching it to a vehicle or building.

[0280] Although the preferred embodiment of the present invention has been described above with reference to the drawings, a person skilled in the art will easily imagine various changes and modifications within the obvious scope upon reading the specification. Therefore, such changes and modifications are interpreted as falling within the scope of the invention as defined by the claims. [Explanation of symbols]

[0281] 100, 200, 300, 400, 500, 600, 700… Antenna Systems 110, 210, 310, 410...Laminate 101, 201, 301, 401, 501, 601, 701…First glass layer 202, 302, 502, 602…Second glass layer 103,203,303,403,113,413…Adhesive layer 503a, 603a, 703a, 213a, 313a...First adhesive layer 503b, 603b, 703b, 213b, 313b...Second adhesive layer 104,114...Circuit layer 105,115…High frequency insulation layer 106, 116…Conductor layer 107, 117...High frequency antenna circuit board 308...Fixing means 408a, 408b…Fixing means 318,418,718…protective layer 409...Adherend

Claims

1. A high frequency antenna circuit board; an adhesive layer adjacent to at least one surface of the high frequency antenna circuit board and made of at least one resin selected from the group consisting of polyvinyl acetal resin and ionomer resin; A protective layer; having One of the outermost layers is composed of the adhesive layer, and the other is composed of the protective layer. Laminate.

2. The laminate of claim 1 , wherein the protective layer is adjacent to the adhesive layer.

3. 3. The laminate according to claim 1, wherein the protective layer is made of glass or polyester resin.

4. 4. The laminate according to claim 1, wherein the adhesive layer adjacent to at least one surface of the high frequency antenna circuit board has a total thickness of 370 μm or less.

5. 5. The laminate according to claim 1, wherein the adhesive layer adjacent to at least one surface of the high-frequency antenna circuit board is made of a polyvinyl acetal resin having a plasticizer content of 0 to 30 mass %.

6. 6. The laminate according to claim 1, wherein the adhesive layer adjacent to at least one surface of the high-frequency antenna circuit board is made of a polyvinyl acetal resin, and the viscosity of a 10% by mass solution of the polyvinyl acetal resin in a toluene / ethanol = 1 / 1 (mass ratio) solution measured at 20°C and 30 rpm using a Brookfield (B-type) viscometer is 100 to 1000 mPa s.

7. A laminate according to any one of claims 1 to 6, wherein an adhesive layer (1) and an adhesive layer (2) are adjacent to each other on both sides of a high-frequency antenna circuit board, the adhesive layer (1) has a total thickness of 370 μm or less, and the adhesive layer (2) has a total thickness of more than 370 μm and 2.5 mm or less.

8. 8. The laminate according to claim 1, wherein the high-frequency antenna circuit board includes an insulating layer made of at least one material selected from the group consisting of a thermoplastic liquid crystal polymer, a polyimide, a polyether ether ketone, a polyphenylene ether, a fluororesin, and a ceramic.

9. 9. The laminate according to claim 1, wherein the high-frequency antenna circuit board is capable of supporting a data transmission speed of 10 gigabits per second or more.

10. A laminate according to any one of claims 1 to 9, which is used to form an antenna system by application to an adherend.

11. The laminate according to claim 10, wherein the adherend is a glass substrate and is bonded via the adhesive layer.

12. A laminate comprising: a high frequency antenna circuit board; and an adhesive layer adjacent to at least one surface of the high frequency antenna circuit board, the adhesive layer being composed of at least one resin selected from the group consisting of polyvinyl acetal resin and ionomer resin; a first glass layer adjacent to the adhesive layer and having a higher dielectric constant than the adhesive layer; An antenna system comprising:

13. 13. The antenna system according to claim 12, further comprising a second glass layer, and the high frequency antenna circuit board is disposed between the first glass layer and the second glass layer via a first adhesive layer and a second adhesive layer, respectively.

14. 14. The antenna system according to claim 12 or 13, wherein the first glass layer is made of at least one selected from the group consisting of soda-lime glass, borate glass, borosilicate glass, aluminosilicate glass, quartz glass, alkali-free glass, and low-alkali glass.

15. 15. The antenna system according to claim 12, wherein the first glass layer has a dielectric constant εg of 3.0 to 7.5, measured at a frequency of 28 GHz, in both a direction in a plane and in a direction perpendicular thereto.

16. 16. The antenna system according to claim 12, wherein the antenna circuit in the high-frequency antenna circuit board is disposed in an area within 10 cm inward from the edge of the glass layer.

17. 17. The antenna system according to claim 12, wherein the first glass layer includes a colored area, and an antenna circuit in the high frequency antenna circuit board is disposed within the colored area.

18. A method for manufacturing the antenna system according to any one of claims 12 to 17, comprising the steps of: laminating a high-frequency antenna circuit board on at least one glass substrate via an adhesive layer and / or adhesive film made of at least one material selected from the group consisting of polyvinyl acetal resins and ionomer resins; A step of heating and pressing the adhesive layer and / or the adhesive film at a temperature equal to or higher than the softening temperature thereof; A method for manufacturing an antenna system comprising:

19. A method for manufacturing an antenna system according to any one of claims 12 to 17, comprising the steps of: a step of interposing a compound absorbable by the adhesive layer between the adhesive layer of the outermost layer of the laminate and a glass substrate, and allowing the adhesive layer to absorb the compound, thereby adhering the laminate to the glass substrate; A method for manufacturing an antenna system comprising:

20. 20. The method of claim 19, wherein the compound is a plasticizer for the adhesive layer.

21. An adhesive film comprising at least one selected from the group consisting of polyvinyl acetal resins and ionomer resins, the adhesive film being used as an adhesive layer in the antenna system according to any one of claims 12 to 17.

Citation Information

Patent Citations

  • Vehicle antenna

    JP2007053505A

  • Antenna sheet and manufacturing method thereof, and antenna enclosed laminated glass and manufacturing method thereof

    JP2009200851A

  • Transferring wiring circuit board, and wiring circuit member

    JP2010135692A

  • Polyvinyl acetal film and uses thereof

    WO2011125791A1

  • Thermoplastic elastomer composition, molded article, and adhesive agent

    WO2015087955A1